Seasonal grazing drives complementary adaptive strategies in grasses and forbs via niche divergence: Evidence from a long-term experiment in alpine meadows - Peng Jiang; Hao-Zhe Zheng; Qing-Shan Fan; Lu-Ji Ade; Shu-Lin Wang; Fu-Jiang Hou (Agriculture, Ecosystems & Environment, 2026)

Projected climate change impacts on crop yields in China's drylands by statistical models and emulators - Shuangshuang Zi; Yiqing Liu; Yan Li; Shuai Wang; Shan Sang; Huiqing Lin; Chengcheng Hou; Fengyu Fu; Bojie Fu (Agricultural Systems, 2026)

Molecular-level transformation of algal organic matter during water treatment processes by FT-ICR MS integrated with reactomics and interpretable machine learning - Wenke Li; Qiguang Shan; Qinglong Fu; Jibao Liu; Mahmoud Nasr; Huiyu Dong; Eunsang Kwon; Manabu Fujii (Water Research, 2026)

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

Indoor environmental quality of underground spaces: Multi-dimensional assessment and interaction effects in a renovated air-raid shelter bookstore in transition season - Ran Cheng; Ting Fu; Hong Hu; Shan Gao; Chi Feng (Building and Environment, 2026)

An automated High-Precision farm mapping pipeline using UAV point clouds - Yongchao Shan; Yanxin Yin; Hao Wang; Guangqiang Zhang; Xiangchen Cao; Yue Zhao; Weiqiang Fu; Zhijun Meng; Chunjiang Zhao (Computers and Electronics in Agriculture, 2026)

Decadal gelatinization and phenological advancement of small jellyfish in Laizhou Bay, Bohai Sea - Ping Fu; Shan Sun; Huichao Jiang; Jianlong He; Ling Cheng; Bo Su; Hongyan Xing; Yuanqing Ma; Lijuan Liu; Yuting Zhao; Juan Zhang; Xiaowen Zhang (Marine Pollution Bulletin, 2026)

Fungal drivers of mycotoxin contamination in wheat: Early warning and plasma-based control - Keyi Zou; Shujuan Chen; Lin Ji; Guoyan Wu; Ke Zhao; Jingxia Fu; Xiumei Yu; Xiaoxue Shan; Likou Zou (Food Research International, 2026)

Multiscale protection of anthocyanin via zein/cinnamaldehyde/sodium alginate core-shell nanoparticles enable UV-stabilized colorimetric label for monitoring shrimp and fish freshness - Zhihang Xu; Hong He; Jian Du; Peng Shan; Chenglong Fu; Jinwen Hu; Yehan Tao; Chao Li; Yanna Lv; Haisong Wang (Food Chemistry, 2026)

Development of ammonia-sensitive carboxymethyl cellulose/pectin colorimetric films with sodium lignosulfonate-regulated ZIF-67 for pork freshness monitoring - Zhihang Xu; Jian Du; Peng Shan; Yali Zhao; Chenglong Fu; Jinwen Hu; Yehan Tao; Chao Li; Yanna Lv; Haisong Wang (Food Bioscience, 2026)

Competitive adsorption-triggered release of cinnamaldehyde from ZSM-5/ZIF-8 nanocarriers in sodium alginate films for early-stage fish preservation - Peng Shan; Hong Wang; Zhihang Xu; Yilin Wang; Chenglong Fu; Jinwen Hu; Yehan Tao; Xiaodong Xia; Jian Du; Haisong Wang (Chemical Engineering Journal, 2026)

Under greenhouse settings, mycorrhizal responsive herbs establish better in their own soil compared to less responsive counterparts - Stavros D. Veresoglou; Yang Liu; Jie Bai; Hanzhi Bao; Peipei Bao; Bolun Cai; Liqun Cai; Jiawei Cao; Chen Chen; Genrun Chen; Hongqiao Chen; Jiarong Chen; et al. (Plant and Soil, 2026)

Finite strain pattern inferred from magnetic fabrics across the southern portion of the Central Range, Taiwan - Ya-Chu Tseng; En-Chao Yeh; Ning-Shan Hui; Yu-Min Chou; Jian-Cheng Lee; Ching-Chou Fu (Tectonophysics, 2026)

First early Toarcian B/Ga paleosalinity record from the eastern Tethyan Ocean: Implications for hydroclimate evolution - Ying Nie; Wei Wei; Yansheng Shan; Shengqiang Zeng; Shuai Zhang; Ahmed Mansour; Rui Wang; Jianguo Yin; Shouji Pang; Fanyang Meng; Shiming Dong; Weihong Pan; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Urinary biomarkers of emerging contaminants in relation to prevalent Parkinson's disease: An exploratory mixture and network toxicology study - Chiqun Shan; Yiming Ge; Junye Bian; Yuli Lin; Bo Fu; Qinru Xiao; Aihua Guo; Mengyan Li; Pan Xu; Yi Chen; Haobo Chen; Shaoyou Lu (Journal of Hazardous Materials, 2026)

pH and polyphenol-controlled release dual-responsive intelligent hydrogel absorbent pad strategy: methylcellulose‑sodium alginate and anthocyanin@MOFs for chilled pork preservation - Yanpei Huang; Conghui Lang; Fei Ren; Jinsheng Fu; Shengmin Liu; Chuang Zhang; Kai Shan; Chunbao Li; Wenxue Chen; Ming Zhang; Qiujin Zhu; Haiming Chen (Food Research International, 2026)

Consumer preferences for simultaneous presentation of nutrition and environmental labelling: Evidence from a discrete choice experiment at UK scale - Rao Fu; Shan Jin; Francisco Areal; Paul Brereton; Jayne V. Woodside; Jelena Vlajic; Beatrice Smyth; Anne P. Nugent; David Livingstone; George Hutchinson; Eva-Leanne Thomas; Leona Lindberg; et al. (Food Quality and Preference, 2026)

Ion-shielded emulsions enabling salt stability and synergistic pH-responsive release for high-salinity food preservation - Peng Shan; Jian Du; Zhihang Xu; Chenglong Fu; Jinwen Hu; Yehan Tao; Chao Li; Jijuan Cao; Dong Lv; Haisong Wang (Food Packaging and Shelf Life, 2026)

Multi-omics analysis of untargeted metabolomics and gut microbiota study on the mechanism of Astragalus-Safflower to coordinate the regulation of energy metabolism pathways and gut microbiota remodeling to improve ischemic stroke - Junmin Fu; Fuyu Liu; Yun Han; Yonggang Feng; Kaixin Shan; Mimi Wang; Xiang Meng; Haibo Zhang; Mingsan Miao; Suxiang Feng; Xiaoyan Fang (Metabolic Brain Disease, 2026)

Paleoproterozoic protracted collisional orogeny: Insights from the Wutai Complex in the central North China Craton - Fengyu Qi; Bo Huang; Xiaoxue Shan; Dong Fu (Precambrian Research, 2026)

Corrigendum to ‘The earliest sponge spicule tufts from the Cambrian Lower Yanjiahe Formation, Three Gorges area, South China’ [Palaeoworld 34 (2025) 200995] - Lei Zhang; Ying Wu; Fan Zhai; Chen-Zhang Duan; Shan-Shan Fu; Shan Chang; Yan Ye; Can Chen; Xia Wang; Xian-Guo Lang; Qing-Lai Feng; Marie-Béatrice Forel (Palaeoworld, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Bionic titanium nitride/silica nanofiber-based aerogels enabling highly efficient and stable solar-water desalination with good salt resistance - Qiuxia Fu; Wenzhe Li; Yuxin Ma; Xiangxiang Gu; Siyuan Xiao; Haoru Shan (Chemical Engineering Journal, 2026)

Co-pyrolyzed biochar enhances soil fertility and crop quality by modulating rhizosphere microbial functional modules - Zhouyang Lin; Jiaqi Li; Yaquan Zhang; Yi Lu; Qingyun Chen; Shengdao Shan; Haifeng Zhuang; Jianzhou Fu (Journal of Soils and Sediments, 2026)

Long-term trends and risk regulation of heat exposure in megacities: seasonal dynamics and determinants - Ziwen Jin; Shuyi Zhang; Ke Zeng; Muyao Ma; Yue Yang; Yuling Fu; Hanxin Tang; Shan Yin; Ji Zheng; Min Liu (Environment, Development and Sustainability, 2026)

Molecular mechanisms underlying the maintenance of protein homeostasis in pearl gentian grouper under acute high-temperature stress - Qiu-Ting Yang; Ren-Xie Wu; Yan-Shan Liang; Ben-Ben Miao; Su-Fang Niu; Feng-Ling Lei; Fan-Li Long; Zhen-Bang Liang; Yu-Xin Shen; Yu Fu (Journal of Thermal Biology, 2026)

Integrating stereoselective synthesis and molecular–behavioral approaches to characterize aggregation pheromone in the German cockroach - Yun Zhou; Jianan Wang; Xiaoyang Li; Jionglin Wang; Yueru Zhang; Xiaochen Fu; Yinan Qi; Jinlong Han; Feng Zhang; Qinghua Bian; Jiangchun Zhong; Chenggang Shan; et al. (Insect Biochemistry and Molecular Biology, 2026)

Wheat-spike-shaped arabinans from Lycium barbarum by alkaline scission-Cascade refinement and its dual-immunomodulatory activity - Wenqi Huang; Yusong Zuo; Xiangyu Fu; Zhichun Yang; Yongqin Liao; Lan Zhang; Wenxian Lan; Shan Liu; Linjuan Huang; Zhongfu Wang; Hong Zhang; Guiping Gong (Food Chemistry, 2026)

A review of early Paleozoic subduction-accretion tectonics in the North Qilian Orogenic Belt, Northeastern Tibet: Implications for the evolution of the Proto-Tethys Ocean - Dong Fu; Bo Huang; Timothy Kusky; Simon A. Wilde; Fengyu Qi; Xiaoxue Shan; Yilin Qu; Hong Wang (Earth-Science Reviews, 2026)

Bioinspired domed cone-pillar nanoarrays design for robust and low-haze-transparent superhydrophobic quartz glass - Yingying Dou; Yue Fan; Qiongwen Fu; Meiling Tao; Junyin Ouyang; Hongtao Liu; Lin Liu; Yabin Yang; Shilin Huang; Shan Zhou; Xuelin Tian (Chemical Engineering Journal, 2026)

Monoterpenoids from the roots of Paeonia lactiflora Pall. and their neuroprotective activity - Bo Fu; Yi-Qiang Zhang; Jin-Ling Zhang; Si-Yi Wang; Jia-Tong Wu; Juan Pan; Wei Guan; Zhi-Chao Hao; Qing-Shan Chen; Li-Li Zhang; Hai-Xue Kuang; Yan Liu (Natural Product Research, 2026)

Sex-specific metabolic reprogramming in Trachinotus blochii under short- and long-term hypoxia - Yue Gu; Yue Chen; Ze Xin Zhong; Fu Cheng Yao; Chun Xiu Jin; Shan Ying Han; Fei Biao Song; Jian Luo; Jun Long Sun (Aquaculture, 2026)

Antibiotic transport and release effects in paddy soil-water system under water level regulation modes - Jian Zhang; Qinglin Li; Renjie Hou; Zhaoqiang Zhou; Qiang Fu; Tianxiao Li; Anshuang Su; Hai Xu; Miao Wang; Wei Huang; Shan Zhao (Water Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

AI-driven protein engineering: A new paradigm for plant trait design - Ran Fu; Shan Jiang; Tianhao Wu; Can Yin; Jun Yan; Xiangfeng Wang (Molecular Plant, 2026)

Socio-economic, structural, and policy drivers of agroforestry in Great Britain - Francisco J. Areal; Kyriaki Remoundou; Beth Clark; Shan Jin; Rao Fu; Felix Eigenbrod; Martin Lukac; Yit Arn Teh; Lynn J. Frewer (Land Use Policy, 2026)

The dual origin of granites from fluid-absent and fluid-fluxed melting of the juvenile lower crust: New constraints from Mo isotopes and phase equilibrium modeling - You-Shan Xia; Guo-Chao Sun; Peng Gao; Zi-Fu Zhao; Yao Zhou; Zhen-Xin Li; Gang Wen; Lei Qin (Geochimica et Cosmochimica Acta, 2026)

A novel strategy for cooked sheep liver preservation: Integrating high-barrier polymer packaging with Cistanche deserticola aqueous extract treatment - Jiahui Du; Jiushi Guo; Ganqi Yang; Boyu Wang; Jie Cao; Tungalag Dong; Terigen Bao; Shan Qing; Ying Fu; Xueyan Yun (Food Control, 2026)

Efficient and selective cesium adsorption via potassium nickel ferrocyanide immobilized in situ Ti3C2TX MXene nanosheets - Chengyun Fu; Ze Huang; Ailin Du; Mark Julian Henderson; Shan Zhu; Minhao Yan (Chemical Engineering Journal, 2026)

Biomimetic nanospheres as a therapeutic intervention for disrupting the infection-ischemia cycle in ischemic limbs - Ruihan Wang; Chen Yuan; Minghao Cai; Shan Lu; Jiaxiang Han; Zhongbo Sun; Yuanqing Kan; Bin Gao; Daqiao Guo; Weiguo Fu; Yisheng Xu; Yi Si (Chemical Engineering Journal, 2026)

Targeted lithium extraction from spent nickel-rich cathodes driven by a hydrogen-induced interfacial “push-pull” mechanism - DeHao Fu; Shan Jin; ChaoHui Chen; YingXiang Zhong; HaoFeng Tan; JunXia Meng; QuanXin Ma (Chemical Engineering Journal, 2026)

Recent developments in braided river morphology of the Tuotuo River in the upper Yangtze River basin - Tingting Jiang; Xinmeng Zheng; Hongsheng Fu; Qianyue Guo; Xingnian Liu; Yuqi Shan; Vladimir I. Nikora; Chao Liu (Environmental Fluid Mechanics, 2026)

Nighttime Atmospheric Pressure Measurement at 80–110 km Altitude over Xi’an by GBAVTII - Cun-Xia Li; Yang-He Liu; Yan Fang; Ning-Ju Hui; Yan-Long Wang; Yi-Shan Zhang; Di-Di Fu; Yuan-He Tang (Applied Geophysics, 2026)

Structurally diverse monoterpenoid indole alkaloids from Damnacanthus hainanensis as well as their potential anti-inflammatory and anti-HIV effects - Gui-Qiong Wu; Long-Cheng Cui; Ye-Ping Liu; Chen-Xu Yue; Lin-Xuan Li; Tian-Yu Wang; Yu-Shan Wang; Shu-Ri Li; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Two new compounds from the roots of Paeonia lactiflora Pall. and their anti-inflammatory effects - Bo Fu; Jin-Ling Zhang; Jia-Tong Wu; Si-Yi Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Zhi-Chao Hao; Hai-Xue Kuang; Qing-shan Chen; Li-Li Zhang; Bing-You Yang; et al. (Natural Product Research, 2026)

Analysis of the morphological structure and metabolic characteristics of Moniezia in sheep - Qian Mu; Wan-Ling Yao; Bao-Shan Wang; Wen-Zhu Chai; Fu-Hua Liu; Zhen Huang; Yong-Cheng Meng; Jing Pan; Xi-Ping Fan; Wan-Hong He; Wang-Dong Zhang (Veterinary Parasitology, 2026)

Comparative evaluation of urine, whole blood, and serum as biological matrices for human biomonitoring of neonicotinoid insecticides and metabolites - Yuli Lin; Junye Bian; Kai Lin; Yiming Ge; Chiqun Shan; Bo Fu; Weizhong Chen; Tao Chen; Qinru Xiao; Bingjun Lu; Qunlin Xiao; Shaoyou Lu (Journal of Hazardous Materials, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Analysis of different fermentation processes of jujube-hawthorn fermented beverage based on untargeted metabolomics and GC–MS - Zhibin Xing; Yueyao Li; Hao Huang; Hexi Yuan; Xiaoqiang Zhang; Xinrui Liu; Chunhui Shan; Xizhe Fu; Yinglin Du (Food Research International, 2026)

Crosstalk-free dual-mode electronic skin enabled by selective electrospinning and machine learning-based decoupling - Chu Qin; Qingyin Sun; Chuheng Fu; Keyi Shan; Yuxin Sun; Min Wang (Chemical Engineering Journal, 2026)

Shape-dependent magnetic-driven microrobots for biofilm-eradicating medical device disinfection through mechanical and chemical bactericidal action - Ke Cheng; Tongfang Fu; Shan Sun; Wenhao Zheng; Jiaming Gong; Jingxin Ma; Yazhou Zhou; Feili Lai; Martin Pumera; Hengwei Lin (Chemical Engineering Journal, 2026)

Mechanisms of flavonoid-mediated amelioration of MASLD: flavonoids, their metabolites or impact on gut microbes? - Ruxuan Chen; Xionghui Wu; Ning Yin; Enjun Xie; Shumin Sun; Jie Shen; Yunmei Chen; Fenghua Zhou; Tao Li; Qili Li; Donglin Su; Fuhua Fu; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Structural diversity and cytotoxic secondary metabolites from the endophytic fungus Chaetomium globosum - Yizhou Bian; Sulu Qin; Shan Ran; Tao Zhu; Haiyan Fu; Wenjing Wang; Xiaolong Yang (Phytochemistry Letters, 2026)

The effect of hydrothermal desulfation of Gracilaria on the physicochemical and structural alterations of gel by different temperatures - Yunshuang Jiao; Weijie Qiu; Baoshang Fu; Pengfei Jiang; Libo Qi; Shan Shang (Food Chemistry, 2026)

Mechanistic-data-driven modeling of multi-material composite columns: Toward intelligent lightweight design - Shan Gao; Jicheng Xu; Feng Fu; Zhenhua Huang; Jean Francois Demonceau; Jie Yang (Engineering Structures, 2026)

Bisphenols and parabens in soils and outdoor dust from a metropolitan city in the Guangdong–Hong Kong–Macao Greater Bay Area, China: concentrations and human exposure risk - Xulong Chen; Xiujuan Qi; Bingjun Lu; Yuli Lin; Bo Fu; Chiqun Shan; Xiangxuan Kong; Kai Lin; Tingting Zhu; Shaoyou Lu (Environmental Monitoring and Assessment, 2026)

Effects of different thawing methods on the physicochemical and structural properties of frozen quinoa dough - Mengqi Jiao; Yingnan Liu; Baoshang Fu; Pengfei Jiang; Chengrong Wen; Libo Qi; Shan Shang (Journal of Cereal Science, 2026)

Space weathering on the lunar nearside and farside revealed by iron and potassium isotopes - Heng-Ci Tian; Wei Yang; Xinmiao Zhao; Jun Du; Liyu Shan; Wen-Jun Li; Jing Wang; Xuhang Zhang; Yangting Lin; Xian-Hua Li; Fu-Yuan Wu (Geochimica et Cosmochimica Acta, 2026)

Arsenic species in crayfish from the Yangtze River basin, China: Levels composition and health risk assessment - Xinjie Li; Bo Fu; Kai Lin; Jiayin Huang; Sisi Yu; Wenchao Zhu; Yuli Lin; Chiqun Shan; Mingqin Zhong; Shaoyou Lu (Aquaculture, 2026)

Foliar application of amino acids enhances grain yield and bread-making quality in wheat (Triticum aestivum L.) - Shaoqing Tan; Shan Fu; Yuanyuan Liu; Wenfei Tian; Jiuliang Xu (Journal of Cereal Science, 2026)

Occurrence, distribution, and potential risk of per- and polyfluoroalkyl substances in soil, outdoor dust, and atmospheric particles in the electronic industrial agglomeration zone in South China - Hanying Zheng; Xulong Chen; Bingjun Lu; Pei Luo; Bei Wang; Chiqun Shan; Bo Fu; Yuli Lin; Muchen Yin; Jiayi Xu; Xiangxuan Kong; Tingting Zhu; et al. (Environmental Pollution, 2026)

Experimental and numerical investigation on seismic performance of seawater sea-sand coral aggregate concrete filled UHPC tubular columns - Chengdong Lu; Dingkuan He; Bo Shan; Peicheng Qin; Tianyu Li; Bin Huang; Xinlin Fu; Gang Liu (Engineering Structures, 2026)

Simultaneous delamination and delithiation of spent LiFePO4 cathode via a sonochemical approach - Zhanpeng Wang; Xinyuan Zhang; Zhen Fu; Shan Chen; Yunxia Zhang; Haimin Zhang; Huijun Zhao (Chemical Engineering Journal, 2026)

From bioprocess to market: Optimizing medium-chain carboxylate extraction for application readiness - Yiran Zhang; Aijie Wang; Yilu Sun; Xuening Zhang; Jianfeng Liu; Wen Wang; Cong Huang; Shaoping Fu; Honggang Deng; Yongping Shan; Jiadong Yu; Xufeng Yuan; et al. (Bioresource Technology, 2026)

Physicochemical and mineralogical constraints on the ecological rehabilitation of coal mine waste - Hui Wu; Songlin Wu; Chenxing Wang; Yige Zhang; Suixiaochen Chen; Wei Fu; Ting-Shan Chan; Duminda Vidana Gamage; Baodong Chen (Plant and Soil, 2026)

Enhancing Surface Water Classification: Integrating Time Series Features and Automated Sampling on Google Earth Engine - Yi Fu; Yunlong Yao; Lei Wang; Yuanqi Shan; Weineng Li; Yuna Liu (Chinese Geographical Science, 2026)

An electrocatalytic dual molecularly imprinted polymer-based biosensor enables femtomolar detection of CD44 without antibodies - Ping Xia; Cheng Chen; Ruifang Bai; Weige Dong; Yuchun Fu; Chungu Zhang; Lianhai Shan; Shun Feng (Analytica Chimica Acta, 2026)

English farmers’ views on agroforestry and agroforestry scheme characteristics: a qualitative analysis of drivers and facilitators of engagement - Clark Beth; J. Areal. Francisco.; Remoundou Kyriaki; Jin Shan; Yit Arn Teh; Fu Rao; Lukac Martin; J. Frewer Lynn (Agroforestry Systems, 2026)
Agroforestry is increasingly recognised for its multifunctional benefits, including ecosystem service delivery, biodiversity enhancement, and landscape improvement. As interest in this type of agriculture grows within new agri-environment policies, understanding farmer preferences and barriers to agroforestry adoption becomes critical. This study explored farmer views on agroforestry practices and scheme characteristics through four focus groups with 24 participants in England. Thematic analysis identified four key themes: terminology, perceived benefits, barriers, and facilitators of adoption. Farmers associated agroforestry with a range of farm-level and environmental benefits, such as shade for livestock, additional income streams, habitat creation, and cultural ecosystem services. However, adoption was constrained by concerns over financial viability, scheme inflexibility, and the mismatch between the long-term nature of tree planting and short-term policy cycles. Farmers also expressed uncertainty about how agroforestry fits within their role as food producers, and highlighted knowledge gaps around scheme requirements and tree management. Short-term tenancy agreements further limited participation. Findings suggest that farmers are more likely to adopt agroforestry when support schemes are flexible, context-sensitive, and supported by trusted advisors. Trust in scheme providers, particularly those perceived as impartial and embedded within the farming community, was found to be a critical factor influencing engagement, especially given widespread scepticism toward government-led initiatives. Future policies should prioritise long-term support, facilitate peer-to-peer learning, and ensure that agroforestry practices complement farm operations and food production goals. By fostering trust, simplifying scheme processes, and aligning agroforestry with farmer identity, policy can more effectively support the transition to sustainable land management.

Stabilization stage dissolved oxygen and contact-stabilization time ratio synergistically govern quorum sensing-mediated sludge bulking in the high-rate contact-stabilization process - Zhongqi Jiang; Shan Qiu; Mengxuan Deng; Mengqi Fu; Zikun Jin; Mu Yuan; Wei Zhang; Chuandong Wu (Water Research, 2026)

Real-world safety of fruquininib in refractory metastatic colorectal cancer: A cross-database study - Qian Guo; Meirong Shan; Yanhua Fu; Ni Li; Chu Wu; Wei Gao (Regulatory Toxicology and Pharmacology, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Incomplete lineage sorting, hybridization and polyploidization blurred phylogenetic relationships of gentians from the Qinghai-Tibetan Plateau - Shan-Shan Sun; Shu-Han Xu; Wen-Jie Yi; Shi-Long Chen; Pan Li; Daiki Takahashi; Harue Abe; Xiao-Lei Ma; Peng-Cheng Fu (Molecular Phylogenetics and Evolution, 2026)

Fuel stratification effects on flame dynamics and combustion instability for strongly coupled stratified flames - Pengfei Fu; Jiacheng Lyu; Jinxiang Zhu; Shan Li; Tengyu Liu; Zhenhai Wang; Zhixin Zhu; Gaofeng Wang (Fuel, 2026)

The role of geography and regional climate in shaping the chemical profiles and biological potentials of Citrus essential oils - Wenbin Xiao; Jiajing Guo; Yanfang Liao; Yanjiao Fu; Zixuan Li; Tongping Zhang; Ting Liu; Yangbo Xiao; Xuebo Shang; Zhipeng Gao; Yang Shan (Food Chemistry, 2026)

Quantitative resolution analysis in seismic imaging: From classical theory to cutting-edge advances - Jidong Yang; Jianping Huang; Hejun Zhu; Jiaxing Sun; Li-yun Fu; George McMechan; Houzhu Zhang; Ru-Shan Wu (Earth-Science Reviews, 2026)

“Two-pronged” active packaging films enable biogenic amine scavenging and controlled Ferulic acid release for pork preservation - Hong Wang; Peng Shan; Jian Du; Chao Li; Yehan Tao; Jinwen Hu; Jie Lu; Chenglong Fu; Xiaodong Xia; Jijuan Cao; Haisong Wang (Chemical Engineering Journal, 2026)

SlMYB2: an R2R3-MYB transcription factor enhancing drought, salt, and cadmium tolerance in Solanum lycopersicum - Shan Fu; Fei Liu; Ying Li; Chunyan Lu; Tiantian Liu; Songzhou Tian; Wei Jin; Pingan Guo; Liang Chen; Xinxin Geng (Plant Cell Reports, 2026)

Brown Adipose Tissue Activation Alleviates Cerebral Ischemia–Reperfusion Injury by Increasing 14–3-3ζ Secretion from Circulating Extracellular Vesicles to Suppress P53 Activity - Hui Yue; Xiaohua Wang; Yue Liu; Yinglian Zhou; Yifei Wang; Xuemei Zhang; Shan Huang; Changsi Ai; Jin Fu; Rui Wang (Molecular Neurobiology, 2026)

Plantation forest stand age affects the characteristics and the chlorine reactivity of soil-derived dissolved organic matter - Xin-Yi Jiao; Su-Ping Liu; Shuang Peng; Zi-Hao Wu; Fu-Qiang Fan; Le Fang; Yan-Chao Jin; Peng Liu; Cai-Shan Wang; Ding Pan; Xue-Rong Wang; Ying-Zhi Ding; et al. (Water Research, 2025)

Nanoconfinement-enhanced lanthanum-biochar composites for simultaneous adsorption and catalytic hydrolysis of organic phosphorus pollutants - Shiyun Xu; Xing Yan; Yuchen Wei; Yanyang Zhang; Wanyi Fu; Zhichao Yang; Chao Shan; Bingcai Pan (Water Research, 2025)

The earliest sponge spicule tufts from the Cambrian Lower Yanjiahe Formation, Three Gorges area, South China - Lei Zhang; Ying Wu; Fan Zhai; Chen-Zhang Duan; Shan-Shan Fu; Shan Chang; Yan Ye; Can Chen; Xia Wang; Xian-Guo Lang; Qing-Lai Feng; Marie-Béatrice Forel (Palaeoworld, 2025)

Optimal matrix identification of parabens, triclosan and triclocarban for biomonitoring: Comparative analysis in urine, whole blood, serum, and plasma - Weizhong Chen; Yuli Lin; Kai Lin; Xiaoru Wu; Chiqun Shan; Bo Fu; Yiran Chen; Junye Bian; Xinjie Li; Xulong Chen; Tao Chen; Guangyu Sun; et al. (Journal of Hazardous Materials, 2025)

Application of microbial electrolysis cells in enrichment of anammox bacteria - Qi Gao; Liang Fu; Jing Wei; Xiao-Chun Wang; Xiang Xiao; Yang-Yang Yu; Liang Cheng; Yu-Hao Qiu; Shan-Wei Li (Journal of Environmental Chemical Engineering, 2025)

On-demand cinnamaldehyde releasing from gelatin-based active hydrogel activated by lactic acid for pork meat preservation: A novel “one-step-ahead” strategy - Peng Shan; Jiaming Wu; Jian Du; Chenglong Fu; Jinwen Hu; Yehan Tao; Jie Lu; Yanna Lv; Xiaodong Xia; Jijuan Cao; Haisong Wang (Food Chemistry, 2025)

Combining untargeted metabolomics and chemometrics to reveal the metabolic profiles of jujube-hawthorn fermented beverages at different fermentation stages - Zhibin Xing; Tarun Belwal; Hao Huang; Xiang Li; Liangxia Han; Yahui Yin; Chunhui Shan; Xizhe Fu; Yinglin Du (Food Chemistry, 2025)

Potassium and phosphorus co-doped g-C3N4 with improved carrier migration for efficient photocatalytic degradation of 2,4-dichlorophenoxyacetic acid under visible light - Shan Liu; Simin Long; Yi Zhao; Zhonglin Chen; Jimin Shen; Gang Fu; Jiaxu Zhang; Jing Kang (Environmental Research, 2025)

An investigation of localized entropy driven cathode electrolyte interphase to a one-step complete deprotonation of ethylene carbonate on Ni-rich layered material of lithium-ion battery - Laurien Merinda; Rio Akbar Yuwono; Fu-Ming Wang; Nae-Lih Wu; Citra Deliana Dewi Sundari; Chusnul Khotimah; Han-Pin Hsieh; Jeng-Kuei Chang; Shu-Chih Haw; Chih-Wen Pao; Jeng-Lung Chen; Qunjie Xu; et al. (Chemical Engineering Journal, 2025)

Roles of Immunity and Endogenous Retroelements in the Pathogenesis of Rheumatoid Arthritis and Treatment Strategies - Mingyang Li; Yuanyuan Sun; Xueting Shan; Yuhong Tong; Yite Fu; Xiang Ma; Zhongxin Sun; Yun Xiang; Yidan Zhu; Tao Wang; Xin Wang; Jufang Zhang; et al. (Functional & Integrative Genomics, 2025)

Efficient socket-based data transmission method and implementation in deep learning - Xin-Jian Wei; Shu-Ping Li; Wu-Yang Yang; Xiang-Yang Zhang; Hai-Shan Li; Xin Xu; Nan Wang; Zhanbao Fu (Applied Geophysics, 2025)

Unlocking the potential of fruit and vegetable waste: Sustainable biomanufacturing strategies for synergistic nutrient recovery and high-value bioproduct synthesis - Ziyi Fan; Zhipeng Gao; Yanjiao Fu; Yanfang Liao; Wenbin Xiao; Yunlong Ding; Chenqi Yang; Xin Li; Gaoyang Li; Donglin Su; Yang Shan; Jiajing Guo (Trends in Food Science & Technology, 2025)

Stage–discharge relationships in vegetated channels with overbank floods - Hongsheng Fu; Yuqi Shan; Marwan A. Hassan; Kejun Yang; Chao Liu (Journal of Hydrology, 2025)

Preparation of stir bars coated with N-modified COFs and application to estrogen detection in dairy products - Xixi Lian; Lianzhi Wang; Jianing Sun; Yingying Fu; Zhengchao Duan; Yazhuo Wang; Che Zhao; Gangqi Cheng; Rui Shan (Food Chemistry, 2025)

Inhibition of physicochemical and structural alterations of gluten proteins by fructo-oligosaccharides on frozen mixed cereal dough - Yingnan Liu; Kaiwen Liu; Tianren Zhang; Pengfei Jiang; Libo Qi; Baoshang Fu; Shan Shang (Food Chemistry, 2025)

Chlorine-anion doping enhances the metal-oxygen covalency of Bi0.5Sr0.5FeO3-δ air electrode: achieving superior catalytic activity for reversible solid oxide cells - Hui Ye; Zhipeng Miao; Yanfeng Fu; Pengkai Shan; Bin Qian; Lin Ge; Han Chen; Yifeng Zheng; Sheng Cui (Chemical Engineering Journal, 2025)

In vitro skin permeation of mitragynine: Optimisation of antioxidants for enhanced drug stability and formulation performance - Yee Shan Sim; Juzaili Azizi; Nelson Jeng-Yeou Chear; Siti Rafidah Yusof; Vikneswaran Murugaiyah; Su Yean Teh; Choon Fu Goh (Drug Delivery and Translational Research, 2025)
The opioid-like characteristics of mitragynine with biased μ-opioid receptor activation are attractive for pain and addiction therapy due to less addictive issue. Our previous work has shown the potential of delivering mitragynine through the skin but drug degradation hindered a reliable understanding of its permeation behaviour. This study aims to optimise the use of antioxidants in both the receptor medium and formulations for in vitro permeation studies of mitragynine (5%w/v) using single solvent systems. The optimised receptor medium with 0.01%w/v of ascorbic acid in phosphate buffer saline was chosen due to a high mitragynine recovery that also allowed the detection of a higher mitragynine amount permeated. Dimethyl sulphoxide and Transcutol ® achieved the highest mitragynine permeation (~ 10 – 15 µg/cm 2 ) and skin fluxes (~ 0.5 – 0.8 µg/cm 2 /h). While Maisine ® and propylene glycol achieved ~ 6 – 8 µg/cm 2 of mitragynine permeated. Labrasol ® and Lauroglycol™ showed a relatively low drug permeation (~ 1 – 4 μg/cm 2 ). Permeation data modelling showed that skin diffusion (high apparent diffusion coefficient) was identified as the major mechanism but skin partitioning (moderate to high apparent partition coefficient) became a determining factor for the overall permeation performance. Mass balance studies revealed low mitragynine recovery (< 80%) owing to solvent-induced degradation. Further optimisation of butylated hydroxytoluene incorporation into gel formulations with selected solvents resulted in excellent drug recovery and enhanced skin permeation, even at lower drug loadings. Overall, this study highlighted the importance of enhanced drug stability with antioxidant, facilitating a more accurate assessment of mitragynine’s skin permeation characteristics. Graphical Abstract

Skin penetration enhancers: Mechanistic understanding and their selection for formulation and design - Yee Shan Sim; Li Ching Wong; Soo Chin Yeoh; Abdulsalam Almashhadani; Bilal Harieth Alrimawi; Choon Fu Goh (Drug Delivery and Translational Research, 2025)

Bioinspired urchin-like AuMnCu nanoreactors: Integrating tip-enhanced electric fields with alloy-tuned interfacial electron for precision photothermal immunoassays - Weijie Gong; Yuechun Li; Bangfeng Fu; Jinrui Shan; Jing Zhou; Sijie Liu; Jing Sun; Leina Dou; Jianlong Wang (Analytica Chimica Acta, 2025)

Citizen preferences for supporting farmers in sustainable rural management: An analysis of five biogeographically differentiated European countries - Rao Fu; Meng Yue; Shan Jin; Lynn J. Frewer (Journal of Rural Studies, 2025)

Freeze-thaw and dry-wet alternation regulate the impacts of Fe-C based passivator on soil heavy metals immobilization - Yuliang Zhang; Pingfeng Fu; Sheng Li; Wei Deng; Shan Li; Wen Ni; Siqi Zhang (Journal of Environmental Chemical Engineering, 2025)

Gestational Multi-metal Exposure in Relation to Anthropometric Birth Outcomes and Maternal Hormonal Profiles: A Deeper Insight Into Sex-Specific and Trimester-Specific Influences - Jinfeng Fu; Zhanlu Lv; Wenchao Zhu; Sisi Yu; Bingjun Lu; Xulong Chen; Chiqun Shan; Yuli Lin; Zhihong Huang; Yao Yao; Shaoyou Lu (Exposure and Health, 2025)

The isolation and immunoprotective efficacy of outer membrane vesicles of Dichelobacter nodosus - Xianjing He; Yu Shi; Jiao Liu; Shan Fu; Baiqi Wang; Bao Li; Yujia Sang; Kai Jiang; Dongbo Sun; Donghua Guo (Veterinary Microbiology, 2025)

Controls of paleosedimentary environments and anthropogenic activities on coastal groundwater salinization: A case study of Laizhou Bay, China - Zhen Cui; Guangquan Chen; Xin Shan; Haitao Zhang; Qingjie Zhou; Tengfei Fu; Hongjun Yu; Xingyong Xu; Shenliang Chen (Marine Geology, 2025)

Unveiling the multifunctional roles of karrikin as a novel phytohormone in cadmium detoxification of bread wheat (Triticum aestivum L.) - Ting Zhou; Yu-shan Xiao; Yong-le Fu; Hao Li; Rui Cui; Ying-na Feng; Zheng-fu Zhou; Ying-peng Hua (Journal of Hazardous Materials, 2025)

Enzyme-assisted dynamic extraction as a promising method to produce high-quality fresh tea juice from summer tea leaves - Yuan-Chao Li; Yan-Qing Fu; Ying Gao; Jie-Qiong Wang; Shan Jin; Yanglong Liu; Jian-Xin Chen; Yong-Quan Xu (Food Chemistry, 2025)

Quality enhancement and metabolic mechanism of fermented sausages with Lactiplantibacillus plantarum and Companilactobacillus alimentarius - Fangrui Han; Qiancheng Wu; Shan Li; Yuting Luo; Zengkang Ding; Tong Luo; Jiesong Liang; Chenxiang Fu; Yingchen Wang; Zhongjie Yu (Food Bioscience, 2025)

Multi-mechanism cross-linking driven chain spacing shortening to construct polysaccharide-based active packaging films with high water resistance and intelligent controlled release - Zhihang Xu; Jian Du; Peng Shan; Yilin Wang; Leping Li; Yehan Tao; Jinwen Hu; Chenglong Fu; Yanna Lv; Zhenglei Jia; Xunyu Song; Haisong Wang (Chemical Engineering Journal, 2025)

Prevalence of Avian Influenza Viruses and Biomolecular Analysis of H9N2 Subtype in Live Poultry Markets from 2021 to 2023 in Changsha, China - Xian Zhang; Yutong Wang; Xiaoyu Li; Zheng Huang; Huiyuan Fu; Ruiqing Pei; Caiying Zhu; Yu Di; Shan Chen; Jingfang Chen; Mingzhong Xu; Xuewen Yang; et al. (Food and Environmental Virology, 2025)

Antithrombotic macrocyclic sesquiterpene pyridine alkaloids from Tripterygium hypoglaucum - Qiong Jin; Jia-Shan Shen; Xian-Run Wu; Hui-Zhen Peng; Zi-Hao Fu; Li-Qiang Chen; Yun-Li Zhao; Min Ye; Xiao-Dong Luo (Phytochemistry, 2025)

Decoding the role of Bacillus: Unraveling the transformation of bioactive compounds during the aging of Pericarpium Citri Reticulatae - Yanjiao Fu; Chao Wang; Zhipeng Gao; Yanfang Liao; Zixuan Li; Wenbin Xiao; Mingwang He; Yuwen Wang; Fuhua Fu; Gaoyang Li; Donglin Su; Lvhong Huang; et al. (Food Research International, 2025)

Nanoparticle-assisted DES-catalyzed green and efficient synthesis of versatile hydrogels for degradable wearable sensors - Jun Hu; Jing Xu; Yuting Tian; Fangjian Shan; Jiangli Wei; Zixun Chen; Xiaoying Xin; Gaojian Chen; Guodong Fu (Chemical Engineering Journal, 2025)

Effects of dry heating and extrusion on physicochemical properties, in vitro digestibility and instant properties of rice, chickpea, and oat flour - Kaiwen Liu; Xiaolin Ao; Pengfei Jiang; Baoshang Fu; Libo Qi; Chengrong Wen; Shan Shang (Food Bioscience, 2025)

Mass spectrometry-based lipidomics combined with flavoromics reveal the mechanism of characteristic flavor formation in Chelidonichthys kumu bone soup treated with different edible oils by frying - Zixi Li; Meng Dong; Libo Qi; Shan Shang; Yan Guo; Lei Qin; Baoshang Fu (Food Bioscience, 2025)

Mold severity and fungal communities in university dormitories: The role of building characteristics and living habits - Qiujia Lai; Ting Fu; Di Huang; Shan Gao; Huan Liu; Ana Sofia Guimarães; Chi Feng (Building and Environment, 2025)

Effect of curvature and taper on the hydrodynamic properties of seal whisker inspired cylinders in uniform flow and wake - Yuanji Yao; Qiao Hu; Long Tang; Tongqiang Fu; Liuhao Shan; Tengyue Li (Ocean Engineering, 2025)

Remediation of As and Sb co-contaminated mine runoff by a pilot-scale aboveground permeable reactive barrier filled with multiple solid wastes-based reactive media - Wei Deng; Pingfeng Fu; Wentao Hu; Shan Li; Yuliang Zhang; Zeen Yu; Jia Li (Journal of Cleaner Production, 2025)

Facile and green synthesis of nanocarriers from chondroitin sulfate-based and whey protein isolate with improved stability and biocompatibility for anthocyanins protection - Zixuan Li; Zhipeng Gao; Donglin Su; Zhipeng Su; Yanjiao Fu; Wenbin Xiao; Fuhua Fu; Gaoyang Li; Lvhong Huang; Jiajing Guo; Yang Shan (Food Chemistry, 2025)

Eco-friendly chitosan-based composite film with anti-dissolution capacity as active packaging for fruit preservation - Jingyi Zhao; Huijie Yang; Chao Li; Zhihang Xu; Peng Shan; Chenglong Fu; Yehan Tao; Jinwen Hu; Haisong Wang; Jian Du (Food Hydrocolloids, 2025)

Effects of tourmaline on anaerobic ammonia oxidation process: Mechanistic Understanding and performance evaluation - Mu Yuan; Xiaohan Jiang; Shan Qiu; Baojian Jing; Shuoqi Ren; Jue Wang; Mengxuan Deng; Mengqi Fu; Zhongqi Jiang; Fengxia Deng; Jinghui Wang; Jie Qiu (Chemical Engineering Journal, 2025)

Genetic Etiology Link to Brain Function Underlying ADHD Symptoms and its Interaction with Sleep Disturbance: An ABCD Study - Aichen Feng; Dongmei Zhi; Zening Fu; Shan Yu; Na Luo; Vince Calhoun; Jing Sui (Neuroscience Bulletin, 2025)

Mass deposition of microbes from wildfire smoke to the sea surface microlayer - Siyao Yue; Yafang Cheng; Lishan Zheng; Senchao Lai; Shan Wang; Tianli Song; Linjie Li; Ping Li; Jialei Zhu; Meng Li; Lianfang Wei; Chaoqun Ma; et al. (Limnology and Oceanography, 2025)
Microbes in the sea surface microlayer (SML) are key to connecting the ocean and the atmosphere, affecting the exchange of matter, momentum, and heat at the interface. However, their sources have never been quantified systematically. Seawater has long been deemed their major source, whereas atmospheric deposition is regarded as trivial or merely providing additional nutrients. Here, combining atmospheric observations and quantitative budget analyses, we show that during the Indonesian peatland wildfire events the smoke can directly deposit abundant microbes into the SML, which can be comparable to the estimated supply from seawater and potentially diversify the microbial community of the SML. This land–air–ocean interaction is relevant for global climate, as it may induce previously unknown effects on the air–sea interactions, especially in an increasingly warming future with more intensifying wildfires.

The dual-targeted transcription factor BAI1 orchestrates nuclear and plastid gene transcription in land plants - Jing Qin; Yelin Shan; Hao Liu; Zhangzhi Xue; Yike Xie; Guoxin Yuan; Yiming Zou; Xiaonuan Hao; Yunpeng Zhu; Xuan Shen; Meng Li; Xu Wang; et al. (Molecular Plant, 2025)

Long-term study of Citrus changshan-huyou Y.B. Chang essential oil: Chemical transformations and their impact on antibacterial efficacy - Wenbin Xiao; Jiajing Guo; Yanjiao Fu; Zixuan Li; Tongping Zhang; Mingwang He; Ting Liu; Yangbo Xiao; Xuebo Shang; Fuhua Fu; Gaoyang Li; Donglin Su; et al. (Food Chemistry, 2025)

Characterization of the Na+-preferential transporter HKT1.1 from halophyte shrub Salix linearistipularis - Shan Fu; Xiuwei Chen; Yanhong Jiang; Shengyue Dai; Haizhen Zhang; Shuang Feng; Aimin Zhou (Physiology and Molecular Biology of Plants, 2025)

Avian influenza A(H5N6) virus detected during live-poultry market surveillance linked to a human infection in Changsha, China, from 2020 to 2023 - Zheng Huang; Rusheng Zhang; Dong Yao; Huiyuan Fu; Lingzhi Li; Shan Xiao; Xinhua Ou; Mingzhong Xu; Qing-Bin Lu; Xuewen Yang (Archives of Virology, 2025)

Iron-assisted anammox process under acidic conditions: A combination of chemical and biological mechanisms - Kunming Fu; Xiaodan Li; Shan Jiang; Yihao Bian; XueQin Li; RuiBao Zhang; Aotong Huo; Teng Guan; Hao Jing; ShengJun Wang (Journal of Environmental Chemical Engineering, 2025)

Insights into potential flavor-active peptides and taste-related compounds in Longjing teas: A comparative study of ‘Longjing 43’ and ‘Qunti’ cultivars - Kangni Yan; Jiatong Wang; Mengxue Zhou; Qunhua Peng; Abdelkader Bassiony Mahmoud; Xue Bai; Susanne Baldermann; Xinbing Jiang; Shan Feng; Yan Wu; Jianyu Fu; Zhi Lin; et al. (Food Chemistry, 2025)

Estimating wastewater emissions and environmental levels of typical organic contaminants based on regionalized modelling - Rui-Xin Qin; Cheng-Zhong Fu; Li Zhuo; Shi-Yi Zhang; Feng-Shan Cai; Kai-Yi Wu; Xiao Yan; Wei-Keng Luo; Min Li; Yun-Gang Shi; Bin Tang (Environmental Research, 2025)

Selective production of olefins from methanol over a heteroatomic SAPO-34 zeolite - Zhaodong Zhu; Mengtian Fan; Meng He; Bing An; Yinlin Chen; Shaojun Xu; Tianze Zhou; Alena M. Sheveleva; Meredydd Kippax-Jones; Lutong Shan; Yongqiang Cheng; Hamish Cavaye; et al. (Science Bulletin, 2025)

Nitrogen utilization dynamics in a tropical estuary: Interplay of temperature and phytoplankton communities - Penglan Shi; Zuoli Tan; Youfei Fu; Min Nina Xu; Rong Zhao; Lihua Shang; Jin-Ming Tang; Lili Han; Shan Sun; Ehui Tan; Zhenzhen Zheng; Shuh-Ji Kao (Marine Environmental Research, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Enhancing NH3-SCR denitrification performance through synergistic A- and B-site effects via CeFe modification of LaMnO3 - Wei Zhang; Qiao Wu; Mengyao Dong; Kang Xie; Yanshan Yin; Yunhe Zhou; Jie Li; Yehao Fu; Yaocheng Liang; Quanbin Song; Min Ruan; Shan Cheng; et al. (Fuel, 2025)

Sea buckthorn polyphenols on gastrointestinal health and the interactions with gut microbiota - Hexi Yuan; Hao Huang; Yinglin Du; Jiaqi Zhao; Shiyang Yu; Yanhong Lin; Yan Chen; Chunhui Shan; Yue Zhao; Tarun Belwal; Xizhe Fu (Food Chemistry, 2025)

Broad-spectrum anti-inflammatory and antioxidant therapy of inflammatory-storm actuated diseases via programmable self-derived cryo-dead neutrophils - Bin Li; Qiuxia Gao; Yunxia Wu; Hongyi Lei; Shengchao Ma; Wei Wang; Hang Sun; Weifeng Ma; Judun Zheng; Chenchen Yuan; Yunlong Zhang; Yue Jia; et al. (Chemical Engineering Journal, 2025)

Acute caffeine supplementation offsets the impairment in 10-km running performance following one night of partial sleep deprivation: a randomized controlled crossover trial - Yi-Shan Tsai; Ting-Tzu Chen; Yau-Ching Chan; Chun-Chin Huang; Ting-Fu Lai; Yung Liao; Richard S. Metcalfe; Yung-Chih Chen; Ho-Seng Wang (European Journal of Applied Physiology, 2025)

The Co‐Infection of ISKNV ‐ II and RGNNV Resulting in Mass Mortality of Juvenile Asian Seabass ( Lates calcarifer ), Zhuhai, Southern China - Qianqian Sun; Shan Ding; Xiangrong Liu; Wenfeng Zhang; Fangzhao Yu; Yuting Fu; Yong Li; Chuanfu Dong (Journal of Fish Diseases, 2025)
Infectious spleen and kidney necrosis virus (ISKNV) and nervous necrosis virus (NNV) are two common and important causative agents in marine‐cultured fish. However, high viral loads of both ISKNV and NNV in the same clinical case is unusual. In this study, a mass mortality event of Asian seabass Lates calcarifer juveniles occurred in Zhuhai, the main Asian seabass cultured area in mainland China. The fish samples were pooled for pathogen identification and both high viral loads of ISKNV and NNV were detected by real‐time microfluidic quantitative PCR and conventional PCR. Immunohistochemistry and immunofluorescence showed that strong ISKNV signals were detected in spleen and liver, while strong NNV signals were detected in brain and eye. The tissue homogenates were inoculated into MFF‐1 cell and SSN‐1 cell, respectively. After several viral passages, both individual ISKNV and NNV were purely isolated from each other, and designated as ASB‐ISKNV‐23 and ASB‐NNV‐23, respectively. The whole genome sequences of ASB‐ISKNV‐23 and ASB‐NNV‐23 were determined and annotated. The result showed that ASB‐ISKNV‐23 and ASB‐NNV‐23 are composed of 112,236 bp and 4441 bp, respectively. Phylogeny analysis showed that ASB‐ISKNV‐23 belongs to ISKNV‐II sub‐genotype and ASB‐NNV‐23 belongs to RGNNV genotype. Collectedly, coinfection of ISKNV‐II and RGNNV were firstly documented in mass mortality of Asian seabass in mainland China. Importantly, both individual ISKNV‐II and RGNNV were purely isolated using two different permissive cell lines. Our study provides useful information for better understanding the complex pathogenesis regarding the coinfection with ISKNV and NNV in farmed fish.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Human cardiac organoid model reveals antibacterial triclocarban promotes myocardial hypertrophy by interfering with endothelial cell metabolism - Nana Yang; Jiahong Chen; Yujie Zhu; Wenxin Shan; Zheng Cao; Yiwen Fu; Huanhuan Cao; Yanyan Li; Yukun Xiang; Shusi Ding; Huiqing Wang; Yaobo Zhao; et al. (Science Bulletin, 2025)

Physicochemical and conformational changes of krill myofibrillar protein induced by two-stage thermal treatment and their relationship with muscle texture - Xiaofang Liu; Kaiwen Liu; Baoshang Fu; Pengfei Jiang; Libo Qi; Shan Shang (Food Chemistry, 2025)

Microbes: Drivers of Chenpi manufacturing, biotransformation, and physiological effects - Yanjiao Fu; Chao Wang; Zhipeng Gao; Yanfang Liao; Mingfang Peng; Fuhua Fu; Gaoyang Li; Donglin Su; Jiajing Guo; Yang Shan (Food Chemistry, 2025)

Bibliometric analysis of microplastics research: Advances and future directions (2020–2024) - Zhilin Xing; Wenting Fu; Liangjie Li; Shan Wu (Continental Shelf Research, 2025)

Highly flexible and enhanced catalytic oxidation of Fe-doped Co3O4/SiOC core-shell heterostructured fibrous membranes for flow-through removal of organic contaminants - Haoru Shan; Wenqiang Wang; Zhirong Wang; Mengjiao Zhang; Yuxin Ma; Wenzhe Li; Qixia Liu; Xinglei Zhao; Jianlong Ge; Qiuxia Fu (Chemical Engineering Journal, 2025)

Application of aqueous two-phase extraction for separation and purification of various adeno-associated viruses - Xiao-Qian Fu; Hui-Yi Leong; Liang-Zhi Qiao; Jia-Nan Zhou; Wei Hu; Shan-Jing Yao; Dong-Qiang Lin (Biotechnology Letters, 2025)

Broad‐Scale Meta‐Analysis of Drivers Mediating Adverse Impacts of Flow Regulation on Riparian Vegetation - Xiaolei Su; María Dolores Bejarano; Roland Jansson; Francesca Pilotto; Judith M. Sarneel; Feng Lin; Yi Wang; Fu Cai; Shan Wu; Bo Zeng (Global Change Biology, 2025)
Over two‐thirds of global rivers are subjected to flow regulation. Although it is widely recognized that flow regulation can adversely affect riparian vegetation—a critical component of river ecosystems—the specific roles of various drivers remain poorly understood. To address this gap, we conducted a broad‐scale meta‐analysis, aiming to elucidate how different factors mediate the adverse impacts of flow regulation on riparian vegetation. This meta‐analysis encompassed 59 papers, spanning 278 dams constructed on 146 rivers. We extracted data on four key indices of riparian vegetation: species richness and abundance of all riparian species, and those indices exclusively for non‐native species. Indices were compared between regulated and free‐flowing or pre‐damming rivers to quantify the impact of flow regulation. Our meta‐analysis revealed a moderate but significant reduction in the richness and abundance of all riparian species under flow regulation, coupled with a strong increase in the abundance of non‐native species. Riparian vegetation in arid and continental climate regions experienced stronger negative impacts than those in tropical and temperate climates. Furthermore, the adverse effects on riparian vegetation were more pronounced downstream of dams than upstream. Considering climate region, study identity, and relative position to the dam as random variables, it became evident that years since flow regulation emerged as the most important factor influencing species richness. Over time, richness gradually recovered from initially low levels. However, this recovery was slowed by increasing flow regulation intensity (percentage of annual runoff stored). Additionally, the impact was more evident in larger rivers. To support regulated river management, we recommend prioritizing the protection of riparian vegetation in arid and continental climates, with emphasis on areas downstream of dams, limiting flow regulation intensity, particularly in larger rivers, and monitoring non‐native species to prevent disproportionate spread.

Dual regulation of As release and soil environment by Fe(Ⅱ) assisted steel slag and coal fly ash: Effects and potential mechanisms - Yuliang Zhang; Pingfeng Fu; Sheng Li; Wei Deng; Shan Li; Wen Ni; Siqi Zhang (Journal of Hazardous Materials, 2025)

Effect of acetylated distarch adipate on fermentation properties of freeze-thawed post-fermented frozen dough and bread characteristics - Man Wang; Xueting Chen; Zuoqian Yang; Miao Wang; Shan Shang; Baoshang Fu; Chengrong Wen (Journal of Cereal Science, 2025)

Fusion of convolutional neural network with XGBoost feature extraction for predicting multi-constituents in corn using near infrared spectroscopy - Xin Zou; Qiaoyun Wang; Yinji Chen; Jilong Wang; Shunyuan Xu; Ziheng Zhu; Chongyue Yan; Peng Shan; Shuyu Wang; YongQing Fu (Food Chemistry, 2025)

Targeted/untargeted metabolomics and antioxidant properties distinguish Citrus reticulata ‘Chachi’ from Citrus reticulata Blanco - Xue Wang; Zhipeng Su; Xiang Li; Jiaxu Chen; Gaoyang Li; Yang Shan; Zhaoping Pan; Fuhua Fu (Food Chemistry, 2025)

Deep eutectic solvent-mediated sunlight polymerization for rapid fabrication of degradable hydrogel-based wearable sensors - Jun Hu; Fangjian Shan; Yuting Tian; Jiangli Wei; Zixun Chen; Weining Liu; Gaojian Chen; Guodong Fu (Chemical Engineering Journal, 2025)

Nanoscale coordination polymer-coated microneedle patches against bacterial biofilm infection via hypoxia-enhanced copper ion interference therapy - Xinwei Fu; Shan Du; Jie Liang; Bo Wang; Yingqi Liu; Yunlong Yu; Liqun Xu; Peng Xue; Bin Wang; Yuejun Kang (Chemical Engineering Journal, 2025)

Breaking the vicious cycle of cellular senescence and ROS via a mitochondrial-targeted hydrogel for aged bone regeneration - Liangmin Fu; Shan Wang; Na Zhang; Yajing Lin; Shihui Zhang; Yingji Mao; Pinghui Zhou (Chemical Engineering Journal, 2025)

Life cycle assessment of hydrogenotrophic denitrification in membrane aerated biofilm reactors for sustainable wastewater treatment - Rui Li; Ming-yi Lu; Rong-bo Guo; Haoran Duan; Bing-jie Ni; Shan-fei Fu (Water Research, 2024)

Comparison of the short- and long-term effects of zinc ions on the anaerobic mesophilic co-digestion of food waste and waste activated sludge: Digester performance, antibiotic resistance gene reduction and the microbial community - Bao-Shan Xing; Yi-Meng Su; Yu-Lin Fu; Yi-Fan Wu; Chen-Hao Yan; Xiaochang C. Wang; Yu-You Li; Rong Chen (Journal of Hazardous Materials, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Insights into novel phosphorus-doped biochar for tetracycline removal: Non-radical oxidation and adsorption - Xi Fu; Xiaojun Niu; Dongqing Zhang; Ling Li; Xingyao Ye; Shan Liao; Maoyu Li; Chuting Lao; Deye Chen; Yu Lin; Zhiquan Yang (Journal of Environmental Chemical Engineering, 2024)

Pre-ozonation coupled with forward osmosis with fertilizer as draw solution for simultaneous wastewater treatment and agricultural irrigation - Fu Yang; Xingbao Wang; Yuanyuan Shan; Chongde Wu; Rongqing Zhou; Nicolas Hengl; Frederic Pignon; Yao Jin (Desalination, 2024)

From agricultural biomass to D form lactic acid in ton scale via strain engineering of Lactiplantibacillus pentosus - Chia-Chi Yang; Chia-Hau Chou; Gia-Luen Guo; Yu-Ju Lin; Fu-Shan Wen (Bioresource Technology, 2024)

A bounding surface model of methane hydrate-bearing carbonate sand-silt mixtures - Lu Ma; Yuzhe Ren; Jincheng Ren; Shan Chang; Xuemin Zhu; Kaiyu Fu; Huan Ye; Bi Sun (Marine Georesources & Geotechnology, 2024)

A single‐nucleus transcriptomic atlas characterizes cell types and their molecular features in the ovary of adult Nile tilapia - Zhi Lei Yao; Xiao Wang; Chun Lei Hu; Fu Xiao Chen; Hong Ju Chen; Shi‐Jin Jiang; Yan Zhao; Xiang Shan Ji (Journal of Fish Biology, 2024)
In fish species, there is limited analysis of signature transcriptome profiles at the single‐cell level in gonadal cells. Here, the molecular signatures of distinct ovarian cell categories in adult Nile tilapia ( Oreochromis niloticus ) were analysed using single‐nucleus RNA sequencing (snRNA‐seq). We identified four cell types (oogonia, oocytes, granulosa cell, and thecal cell) based on their specifically expressed genes and biological functions. Similarly, we found some key pathways involved in ovarian development that may affect germline–somatic interactions. A cell‐to‐cell communication network between the distinct cell types was constructed. We found that the bidirectional communication is mandatory for the development of germ cells and somatic cells in fish ovaries, and the granulosa cells and thecal cells play a central regulating role in the cell network in fish ovary. Additionally, we identified some novel candidate marker genes for various types of ovarian cells and also validated them using in situ hybridization. Our work reveals an ovarian atlas at the cellular and molecular levels and contributes to providing insights into oogenesis and gonad development in fish.

Petrogenesis of late Early Cretaceous adakitic rocks in the offshore Bohai Bay Basin, Eastern China, and tectonic implications - Mao Fu; Chunqiang Xu; Xuanlong Shan; Xintao Zhang; Bin Wang; Chenjie Wang; Jian Yi (International Geology Review, 2024)

Unraveling the toxicity mechanisms of nanoplastics with various surface modifications on Skeletonema costatum: Cellular and molecular perspectives - Ting-Ting Xu; Zhen-Liang Li; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Tao Li; Eddy Y. Zeng; Ke-Fu Yu; Xiang-Rong Xu (Science of The Total Environment, 2024)

Identification and performance of endophytic actinobacteria Ahn65 with functions of growth promotion and disease resistance for rice - Hua Yang; Zhan Hu; Rong Xiao; Zhu-dong Liu; Min Zhang; Yi-Lu Li; Shan-dong Wu; Zu-jiao Fu (Physiological and Molecular Plant Pathology, 2024)

Indicative impacts of sludge properties and biological metabolic characteristics on high-rate contact stabilization process performance - Zhongqi Jiang; Mengxuan Deng; Shan Qiu; Mengqi Fu; Mu Yuan; Qinxue Wen; Xinghua Jia (Journal of Environmental Management, 2024)

The association of mixed multi-metal exposure with sleep duration and self-reported sleep disorder: A subgroup analysis from the National Health and Nutrition Examination Survey (NHANES) - Zifan Zhu; Yongjun Wang; Yuanlong Wang; Maoling Fu; Xinxin Luo; Guojun Wang; Jian Zhang; Xiujuan Yang; Wei Shan; Cunxue Li; Tiebang Liu (Environmental Pollution, 2024)

Effects of tourmaline on the establishment, idling, and recovery of partial nitrification: Mechanistic understanding and performance evaluation - Mu Yuan; Xiaohan Jiang; Baojian Jing; Jue Wang; Mengqi Fu; Mengxuan Deng; Shuoqi Ren; Zhongqi Jiang; Fengxia Deng; Shan Qiu (Chemical Engineering Journal, 2024)

Quinosumycin, a novel anti-MRSA thioether-linked quinolinone-quinazolinone heterodimer from a marine actinomycete Streptomyces diastaticus NBU2966 - Shuangling Tan; Yang Liu; Haonan Fu; Yutong Xue; Fangjian Feng; Jinling Li; Xiaojun Yan; Sitong Wu; Shan He; Lijian Ding (Journal of Oceanology and Limnology, 2024)

Correction: The functional diversity of plants dispersed via three upland rivers in humid subtropical monsoon climate - Rongyan Qian; Fu Cai; Yi Wen; María D. Bejarano; Shan Wu; Qin Yang; Xiaolei Su (Hydrobiologia, 2024)

The functional diversity of plants dispersed via three upland rivers in humid subtropical monsoon climate - Rongyan Qian; Fu Cai; Yi Wen; María D. Bejarano; Shan Wu; Qin Yang; Xiaolei Su (Hydrobiologia, 2024)

Progress in the application of novel cryoprotectants for the stabilization of myofibrillar proteins - Shan Shang; Yueyue Wang; Pengfei Jiang; Baoshang Fu; Xiuping Dong; Libo Qi (Critical Reviews in Food Science and Nutrition, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Citrus aurantium L. 'Daidai' physiological premature fruit drop relieves obesity in high-fat-diet-fed mice via modulating lipid metabolism and gut microbiota - Mingfang Peng; Chao Wang; Zhipeng Gao; Fuhua Fu; Gaoyang Li; Donglin Su; Lvhong Huang; Jiajing Guo; Yang Shan (Food Bioscience, 2024)

Remediation of As, Sb, and Pb co-contaminated mining soils by using Fe/C based solid wastes: Synergistic effects and field applications - Yuliang Zhang; Pingfeng Fu; Sheng Li; Wei Deng; Wen Ni; Siqi Zhang; Longyan Guo; Shan Li; Xiaofei Wang (Chemical Engineering Journal, 2024)

Remediation of multiple heavy metals contaminated soils by Mn and Fe-added solid wastes: Effect and mechanisms - Yuliang Zhang; Pingfeng Fu; Sheng Li; Wei Deng; Longyan Guo; Shan Li; Xiaofei Wang (Chemical Engineering Journal, 2024)

Allelopathy research on the continuous cropping problem of poplar (populus) - Tao Song; Jia-Xu Chen; Lin-Miao Shan; Yu-Chen Qian; Mo-Xian Chen; Jian-Gang Han; Fu-Yuan Zhu (Phytochemistry Reviews, 2024)

Cytotoxic xanthanolide sesquiterpenes from the fruits of Xanthium italicum Moretti - Yu-Tong Li; Cheng-Yong Tan; Jiang Fu; Hai-Qiang Wang; Yun-Bao Liu; Shuang-Gang Ma; Yong Li; Jing Qu; Shi-Shan Yu (Phytochemistry, 2024)

Effect of exogenous protein substitution in glutinous rice cake: Batter rheology, structure, and retrogradation behavior - Yingnan Liu; Shulei Yu; Pengfei Jiang; Baoshang Fu; Libo Qi; Shan Shang (Journal of Cereal Science, 2024)

Advances in the delivery and application of antimicrobial peptide-based nanomaterials - Haoran Deng; Shaohua Zhang; Yanxue Fu; Na Dong; Chongpeng Bi; Anshan Shan; Changxuan Shao (Chemical Engineering Journal, 2024)

New approach for raw biogas: Production of single cell protein by sulfide-tolerant methane-oxidizing bacteria consortia - Hai-Ming Huang; Zhi-Xin Xue; Yu-Feng Jiang; Rui Li; Rong-Bo Guo; Xiao-Lei Fan; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Sodic adakitic granites in the East Kunlun Orogen, China: Partial melting of ultrahigh-pressure metamorphic terranes during continental collision - Lei Qin; Guo-Chao Sun; Peng Gao; Zi-Fu Zhao; Li-Qun Dai; Gang Wen; You-Shan Xia; Yao Zhou (Chemical Geology, 2024)

Rice Yield and Nitrogen Use Efficiency: Different Responses to Soil Organic Matter between Early and Late Rice - Yong Wang; Gang Tang; Wentao Fu; Jin Chen; Shan Huang; Yanni Sun (Journal of Soil Science and Plant Nutrition, 2024)

Reclassification of Streptomyces violarus (Artamonova and Krassilnikov 1960) Pridham 1970 as a Later Heterotypic Synonym of Streptomyces violaceus (Rossi Doria 1891) Waksman 1953 using a Polyphasic Approach - Pei-Lan Long; Yin-Feng Wang; Li Fu; Yan Xiao; Shan-Guang Tang; Jian Gao (Current Microbiology, 2024)

First identification of Mid-Miocene north–south trending dikes in the eastern Qiangtang terrane, eastern Tibet: Mantle melting and implications for plateau uplift - Chuan-Bing Xu; Jun Wang; Qiang Wang; Andrew C. Kerr; Wu-Fu Li; Jin-Heng Liu; Bing-Zhang Wang; Shan-Ping Li; Chun-Tao Wang; Zi-Long Wang; Lin Gong (Lithos, 2024)

Effects of agricultural mulch film on swine manure composting: Film degradation and nitrogen transformation - Zhiqiang Chen; Jie Ren; Zerui Yun; Qinxue Wen; Qiqi Fu; Shan Qiu (Bioresource Technology, 2024)

Lanthanum-modified pyroaurite as a geoengineering tool to simultaneously sink Microcystis cyanobacteria and immobilize phosphorus in eutrophic water - Zhaoyang Shen; Mengjie Zhou; Yanyang Zhang; Xudong Sun; Bo Kong; Wanyi Fu; Zhichao Yang; Chao Shan; Bingcai Pan (Science of The Total Environment, 2024)

Eocene rhyolites in the Shanglaxiu-Xialaxiu area of north-eastern Qiangtang Block, Tibet: Partial melting of juvenile crust? - Yi-Wen Wei; Jun Wang; Qiang Wang; Bing-Zhang Wang; Andrew C. Kerr; Wu-Fu Li; Shan-Ping Li; Jin-Heng Liu; Chun-Tao Wang; Zi-Long Wang (Lithos, 2024)

Differential accumulation patterns of flavor compounds in Longjing 43 and Qunti fresh leaves and during processing responding to altitude changes - A. Bassiony; Qunhua Peng; Susanne Baldermann; Shan Feng; Kangni Yang; Yongcheng Zhang; Jianyu Fu; Haipeng Lv; Zhi Lin; Jiang Shi (Food Research International, 2024)

The boom era of emerging contaminants: A review of remediating agricultural soils by biochar - Renjie Hou; Jian Zhang; Qiang Fu; Tianxiao Li; Shijun Gao; Rui Wang; Shan Zhao; Bingyu Zhu (Science of The Total Environment, 2024)

Sustainable treatment of aquaculture water employing fungi-microalgae consortium: Nutrients removal enhancement, bacterial communities optimization, emerging contaminants elimination, and mechanism analysis - Rui Mi; Xuda Wang; Ying Dong; Shilei Li; Zelong Zhao; Xiaoyan Guan; Jingwei Jiang; Shan Gao; Zhiyu Fu; Zunchun Zhou (Science of The Total Environment, 2024)

Optimization of flavonoids extracted from hawthorn （Crataegus pinnatifida） by ultrasonic-assisted deep eutectic solvent - Xiaojing Sun; Meiling Fu; Shihao Lou; Dandan Li; Xue Han; Shan Gao; Jianhua Xiu; Junfeng Wang; Yuanyuan Ren (Food Bioscience, 2024)

Alkaloids from the stems of Fissistigma maclurei Merr. inhibit the proliferation of synoviocytes - Mu-Tao Liang; Xiao-Zheng Zhang; Zi-Hao Chen; Chuan-Shan Fu; Duo-Jiang Li; Guo-Ze Chen; Ji-Ling Yi; Xue-Ming Zhou (Natural Product Research, 2024)

Stage–discharge relationship in an erodible compound channel with overbank floods - Hongsheng Fu; Yuqi Shan; Kejun Yang; Yakun Guo; Chao Liu (Journal of Hydrology, 2024)

Lemon essential oil nanoemulsions: Potential natural inhibitors against Escherichia coli - Wenbin Xiao; Zhipeng Gao; Ting Liu; Weiming Zhong; Sifan Jiang; Mingwang He; Fuhua Fu; Gaoyang Li; Donglin Su; Jiajing Guo; Yang Shan (Food Microbiology, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

Optimization of alkaline hydrothermal treatment for humic acids production from corn straw digestate using the response surface methodology - Shuai-Ze Han; Bo-Tao Zhang; Man-Qian Wang; Rong-Bo Guo; Shan-Fei Fu (Journal of Environmental Chemical Engineering, 2024)

Inhibition of protein denaturation and oxidation of prepared shrimp paste by sturgeon skin collagen peptide - Yueyue Wang; Xiaofang Liu; Pengfei Jiang; Libo Qi; Baoshang Fu; Shan Shang (Food Bioscience, 2024)

Phthalate drives splenic inflammatory response via activating HSP60/TLR4/NLRP3 signaling axis-dependent pyroptosis - Xin-Ran Ge; Yi Zhao; Hao-Ran Ren; Fu-Wei Jiang; Shuo Liu; Ming Lou; Yi-Feng Huang; Ming-Shan Chen; Jia-Xin Wang; Jin-Long Li (Environmental Pollution, 2024)

Two undescribed benzopyran derivatives from Ranunculus sceleratus L. with their in vitro anti-inflammatory activity in lipopolysaccharide-activated RAW 264.7 cells - Zhen Shi; Si-jia Zhou; Qun-lin Zhang; Fu-cai Ren; Shan-shan Cao; Long-kang Cao; Ya-zhong Zhang; Wen-ming Cheng (Natural Product Research, 2024)

Tourmaline mediated enhanced autotrophic denitrification: The mechanisms of electron transfer and Paracoccus enrichment - Mengqi Fu; Shan Qiu; Jue Wang; Yingshi Zhu; Mu Yuan; Liang Wang (Science of The Total Environment, 2024)

Ultra-low electrical loss superconducting cables for railway transportation: Technical, economic, and environmental analysis - Yu Chen; Lin Fu; Xiaoyuan Chen; Shan Jiang; Xiaohong Chen; Junqi Xu; Boyang Shen (Journal of Cleaner Production, 2024)

Analysis of amino acid enantiomers in ambient aerosols: Effects and removal of coexistent aerosol matrix - Ying Li; Xiaoying Li; Libin Wu; Luhan Shi; Shan Wang; Pingqing Fu; Yingyi Zhang; Senchao Lai (Journal of Environmental Sciences, 2024)

Insights into major pigment accumulation and (non)enzymatic degradations and conjugations to characterized flavors during intelligent black tea processing - Yongcheng Zhang; Kangni Yan; Qunhua Peng; Shan Feng; Zhangfeng Zhao; Long Chen; Lin Ye; Jianyu Fu; Haipeng Lv; Dan Mu; Chunwang Dong; Zhi Lin; et al. (Food Chemistry, 2024)

Has Rural E-Commerce Increased Potato Farmers’ Income? Evidence from the Potato Home of China - Shan Zheng; Lianghong Yu; Huanqing Fu (Potato Research, 2024)

Kelp breeding in China: Challenges and opportunities for solutions - Zi‐Min Hu; Ti‐Feng Shan; Quan‐Sheng Zhang; Fu‐Li Liu; Alexander Jueterbock; Gaoge Wang; Zhong‐Min Sun; Xiang‐Yu Wang; Wei‐Zhou Chen; Alan T. Critchley; Nai‐Hao Ye (Reviews in Aquaculture, 2024)
Breeding has played an important role in the mariculture and industrialization of kelp in China. However, the current kelp breeding systems in China have encountered some problems relating to germplasm diversity, management, technological innovations, and regional co‐operation. This review summarizes the main challenges, such as top‐down and fragmented management of germplasm libraries, as well as private industry breeding without government regulations, inter‐cultivar accidental admixing and genetic erosion, loss of heterozygosity due to repeated selection and self‐crossing. We outline multiple potential approaches to breed cultivars with improved qualitative/quantitative traits which can be subjected to changing environments, for example: (i) establishing a national germplasm repository to enhance integrative collection and preservation of kelp resources; (ii) planning and implementing kelp breeding programmes according to strategic priorities and goal‐orientations; (iii) optimizing a hybridization‐based breeding pipeline to produce robust cultivars through the introgression of novel alleles and thus the expression of hybrid vigour; (iv) enriching the high‐quality annotated reference genomes and functional analysis of trait‐associated markers/loci to develop DNA‐based breeding technologies; (v) developing new priming‐based (e.g., thermal and disease resistance) bio‐engineering breeding strategies to meet future unpredictable climate change; and (vi) breeding towards an ecological kelp‐microbiome interaction‐based technique to produce cultivars with enhanced performance and adaptability to environmental scenarios. Collectively, the lessons learned from kelp breeding in China and the solutions proposed here may not only potentially improve or re‐invigorate the Chinese kelp industry, but will also assist other developing countries in taking corrective actions to develop a sustainable future kelp farming industry.

Larger hydroxyapatite aggregation from Ca2+ adhesion in ANAMMOX granular sludge caused by high dissolved oxygen - Mu Yuan; Shan Qiu; Mengqi Fu; Mengxuan Deng; Jue Wang; Fengxia Deng (Chemosphere, 2024)

Multi-scale failure mechanisms of hydraulic engineering exposed to seasonally frozen salinization environment: Integrating SBAS-InSAR and mechanical experiments - Zhaoxi Wang; Chen Cao; Qingbo Yu; Qing Wang; Cencen Niu; Jiejie Shen; Kuanxing Zhu; Jing Liu; Mengxia Han; Huicheng Fu; Xun Sun; Weitong Xia; et al. (Science of The Total Environment, 2024)

The differences in plant invasion in two types of shorelines under flow regulation of the Three Gorges Reservoir - Yi Wen; Xiaolei Su; Fu Cai; Rongyan Qian; María Dolores Bejarano; Shan Wu; Qin Yang; Xudong Liu; Bo Zeng (Science of The Total Environment, 2024)

Integrated transcriptomic, proteomic, and metabolomic approaches reveal the antifungal mechanism of methyl ferulate against Alternaria alternate - Hui Kong; Shuai Ge; Xia Chang; Saiqing Xu; Haishan Xu; Xincheng Fu; Rongrong Wang; Zisheng Luo; Yang Shan; Shenghua Ding (Postharvest Biology and Technology, 2024)

Diisoprenyl-cyclohexene-type meroterpenoids from a mangrove endophytic fungus Aspergillus sp. GXNU-Y65 and their anti-nonalcoholic steatohepatitis activity in AML12 cells - Feng Qin; Li Luo; Yu-Chen Liu; Xiang-Long Bo; Fu-Rong Wu; Fan-Fan Wang; Mei-Jing Tan; You-Quan Wei; Xiao-Bing Dou; Cai Yi Wang; Xi-Shan Huang; Heng-Shan Wang (Phytochemistry, 2024)

Biogas upgrading by biotrickling filter: Effects of temperature and packing materials - Jie-Hua Huang; Xiao-Lei Fan; Rui Li; Meng-Ting Sun; Hua Zou; Yi-Feng Zhang; Rong-Bo Guo; Shan-Fei Fu (Chemical Engineering Journal, 2024)

High-density lipoprotein cholesterol is associated with lowered cognitive recovery among acute ischemic stroke patients with mild cognitive impairment - Rui Wang; Zhuomin Jiao; Anxin Wang; Yijun Zhang; Xiangxiang Hong; Shan Huang; Jin Fu; Yinglian Zhou; Yifei Wang; Chunyang Li; Yue Liu; Ke Wei; et al. (Acta Neurologica Belgica, 2024)

Exploring the interference mechanisms of surface and aqueous complexes with groundwater arsenate and arsenite adsorption - Shan Hu; Jingyi Fu; Shenmin Zhou (Environmental Science and Pollution Research, 2024)

Exogenous stimulation-induced biosynthesis of volatile compounds: Aroma formation of oolong tea at postharvest stage - Lin Zeng; Shan Jin; Yan-Qun Xu; Daniel Granato; Yan-Qing Fu; Wei-Jiang Sun; Jun-Feng Yin; Yong-Quan Xu (Critical Reviews in Food Science and Nutrition, 2024)

Energy management for proton exchange membrane fuel cell-lithium battery hybrid power systems based on real-time prediction and optimization under multimodal information - Linghong Zeng; Jun Fu; Chuang Sheng; Beijia Li; Ziang Guo; Qian Xiang; Jingjing Wang; Xinkai Shan; Xiaowei Fu; Zhonghua Deng; Zhuo Wang; Xi Li (Journal of Cleaner Production, 2024)

Comprehensive analysis of pigment alterations and associated flavor development in strip and needle green teas - Yongcheng Zhang; Kangni Yan; Qunhua Peng; Susanne Baldermann; Yin Zhu; Weidong Dai; Shan Feng; Jesus Simal-Gandara; Jianyu Fu; Haipeng Lv; Zhi Lin; Jiang Shi (Food Research International, 2024)

Metabolic diversity shapes vegetation-enhanced methane oxidation in landfill covers: Multi-omics study of rhizosphere microorganisms - Shangjie Chen; Wenting Fu; Limin Cai; Zhilin Xing; Baozhong Mou; Yongqiong Wang; Shan Wu; Tiantao Zhao (Waste Management, 2023)

Monazite and titanite U Pb ages of granitoids from the North Qinling Terrane: Implications for the subduction of the Shangdan Ocean and accretionary processes - Zheng-wei Qin; Wolfgang Siebel; Jian-ming Fu; Hao Wang; Bo Bao; Yu-shuai Yu; Liang Shan; You-yue Lu; Yuan-Bao Wu (Lithos, 2023)

Lidocaine pretreatment attenuates inflammatory response and protects against sepsis-induced acute lung injury via inhibiting potassium efflux-dependent NLRP3 activation - Kai Su; Xin-Tao Li; Fang-Xiao Hong; Mu Jin; Fu-Shan Xue (Inflammation Research, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Drivers of low-carbon practices in green supply chain management in construction industry: An empirical study in China - Chun Fu; Ya-Qi Liu; Ming Shan (Journal of Cleaner Production, 2023)

Scene-aware refinement network for unsupervised monocular depth estimation in ultra-low altitude oblique photography of UAV - Kailong Yu; Hao Li; Linjie Xing; Tao Wen; Die Fu; Yang Yang; Chengjiang Zhou; Rong Chang; Shan Zhao; Lin Xing; Haicheng Bai (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Carbonate lithium isotope systematics indicate cooling triggered mass extinction during the Frasnian-Famennian transition - Yang-Yang Wang; Kun Liang; Yilin Xiao; Bo Chen; Erhao Shan; Tingyu Yang; Meng Zhang; He Sun; Hai-Ou Gu; Fengtai Tong; Lulu Fu; Dong-Yong Li; et al. (Global and Planetary Change, 2023)

Planktonic microbial community and biological metabolism in a subtropical drinking water river-reservoir system - Lin Liu; Yu Xin; Shan-Bin Guang; Guo-Fu Lin; Chao-Xiang Liu; Li-Qin Zeng; Shao-Qin He; Yu-Ming Zheng; Guan-Yu Chen; Quan-Bao Zhao (Environmental Research, 2023)

Antibiotic resistant genes profile in the surface water of subtropical drinking water river-reservoir system - Lin Liu; Shan-Bin Guang; Yu Xin; Jie Li; Guo-Fu Lin; Li-Qin Zeng; Shao-Qin He; Yu-Ming Zheng; Guan-Yu Chen; Quan-Bao Zhao (Environmental Pollution, 2023)

Precise classification and regional delineation of maturity groups in soybean cultivars across China - Wenwen Song; Luping Liu; Shi Sun; Tingting Wu; Haiyan Zeng; Shiyan Tian; Bincheng Sun; Wenbin Li; Lijun Liu; Shuming Wang; Han Xing; Xin’an Zhou; et al. (European Journal of Agronomy, 2023)

Magmatic fluids responsible for lode gold mineralization in the giant Linglong deposit at Jiaodong, North China Craton: Constraints from LiO isotopes - Shao-Rui Zhao; Zhan-Ke Li; Zu-Wei Lin; Jian-Feng Gao; Hua-Shan Sun; Martin Yan Hei Li; Xin-Fu Zhao (Chemical Geology, 2023)

Microorganisms regulate soil phosphorus fractions in response to low nocturnal temperature by altering the abundance and composition of the pqqC gene rather than that of the phoD gene - Qingwen Shi; Qiaobo Song; Xuan Shan; Xiaoxia Li; Shuang Wang; Hongdan Fu; Zhouping Sun; Yufeng Liu; Tianlai Li (Biology and Fertility of Soils, 2023)

Carbon emissions induced by land use and land cover change amid rapid urbanization in Chengdu-Chongqing economic circle, China: efficiency, transfer and process - Zhonglin Tang; Shan Ma; Min Fu; Yuting Wang; Jingyue Xue; Yuanfu Yin; Yang Xiao (Environment, Development and Sustainability, 2023)

Response of the nitrogen processing bacterial community to water level fluctuation and nitrate availability in an intact marsh soil column - Yuanqi Shan; Yi Fu; Lei Wang; Yunlong Yao (Environmental Science and Pollution Research, 2023)

Effective removal of cesium by ammonium molybdophosphate–polyethylene glycol magnetic nanoparticles - Chengyun Fu; Zhaomin Tan; Jianfeng Cheng; Jingli Xie; Xuezhi Dai; Yinyuan Du; Shan Zhu; Shaoqing Wang; Minhao Yan (Journal of Environmental Chemical Engineering, 2023)

The effect of bubble size in descaling process of bubble flow pipes based on leaky ultrasonic guided waves - Zhigang Qu; Yunkun Fu; Quanpeng Zhang; Yang An; Xiaopeng Wang; Xin Shan; Yuan Sun; Jianyin Zhao (Desalination, 2023)

Influences of humic acids released during sludge thermal hydrolysis on anaerobic digestion: New insights from enzymatic perspectives - Fang Huang; Hongbo Liu; Jiaxin Wen; Shan Huang; Zhiyong Zheng; Xuedong Zhang; Bo Fu; Yajie Li; Aijie Wang; He Liu (Chemical Engineering Journal, 2023)

Effects of size and surface charge on the sedimentation of nanoplastics in freshwater - Honglu Zhu; Xiaolei Fan; Hua Zou; Rong-Bo Guo; Shan-Fei Fu (Chemosphere, 2023)

RIN enhances plant disease resistance via root exudate-mediated assembly of disease-suppressive rhizosphere microbiota - Keming Yang; Ruixin Fu; Haichao Feng; Gaofei Jiang; Omri Finkel; Tianyu Sun; Mingchun Liu; Baowen Huang; Shan Li; Xiaofang Wang; Tianjie Yang; Yikui Wang; et al. (Molecular Plant, 2023)

Plant facilitation improves carbon production efficiency while reducing nitrogen input in semiarid agroecosystem - Wei Wang; Meng-Ying Li; Shuang-Guo Zhu; Aziz Khan; Xiu-Ping Tao; Guang-Fu Huang; Hai-Ying Liu; Wei Zhang; Hong-Yan Tao; Dong-Shan Gong; Chao Song; You-Cai Xiong (CATENA, 2023)

Magnesium–oxygen isotope constraints on the origin of rodingites in oceanic lithosphere - Mei-Shan Zhao; Yi-Xiang Chen; Jia-Wei Xiong; Xin-Yue Qiao; Yong-Fei Zheng; Wen-Yong Duan; Fang Huang; Zi-Fu Zhao (Chemical Geology, 2023)

Urban agglomeration waterlogging hazard exposure assessment based on an integrated Naive Bayes classifier and complex network analysis - Mo Wang; Xiaoping Fu; Dongqing Zhang; Siwei Lou; Jianjun Li; Furong Chen; Shan Li; Soon Keat Tan (Natural Hazards, 2023)

Occurrences and fates of per- and polyfluoralkyl substances in textile dyeing wastewater along full-scale treatment processes - Yuqian Jia; Chao Shan; Wanyi Fu; Si Wei; Bingcai Pan (Water Research, 2023)

Dihydromyricetin attenuates cisplatin-induced acute kidney injury by reducing oxidative stress, inflammation and ferroptosis - Zheming Xu; Minjing Zhang; Wenwen Wang; Suhan Zhou; Minghua Yu; Xingyu Qiu; Shan Jiang; Xiaohua Wang; Chun Tang; Shuijie Li; Chih-Hong Wang; Runzhi Zhu; et al. (Toxicology and Applied Pharmacology, 2023)

Genomic analysis of Marinomonas algicola SM1966T reveals its role in marine sulfur cycling - Min Zhang; Xiao-Di Wang; Yue Lin; Shu-Yan Wang; Shan Zhang; Jin Cheng; Mei-Ling Sun; Peng Wang; Hui-Hui Fu; Chun-Yang Li; Nan Zhang (Marine Genomics, 2023)

A model for predicting the grain size distribution of an armor layer under clear water scouring - Hongsheng Fu; Yuqi Shan; Chao Liu (Journal of Hydrology, 2023)

NIR responsive composite nanomaterials with in-situ deposition of cascaded nanozymes for multiple synergistic therapy of bacterial infection in diabetic mice - Yan Zhang; Chunping Wen; Yijun Liu; Anqi Li; Qiuyan Guo; Xuan Zhang; Li Fu; Shan Xu; Dan Qiao; Pengwu Zheng; Wufu Zhu; Qingshan Pan (Chemical Engineering Journal, 2023)

Prediction of TBM boring speed based on IPSO-LSSVM parameter optimization algorithm - Zhipeng Lu; Kebin Shi; Renyi Shi; Tao Fu; Jianming Zhang; Hongze Shan (Arabian Journal of Geosciences, 2023)

Effects of adding different ratios of residual sludge and food waste co-anaerobic fermentation liquid to AAO wastewater treatment process - Junhao You; Shilong Tang; Yongchen Zong; Hongtao Shan; Jun Wang; Chunhui Fu (Journal of Water Process Engineering, 2023)

Carbonaceous nanofibrous membranes with enhanced superhydrophilicity and underwater superoleophobicity for effective purification of emulsified oily wastewater - Hong Chen; Anqi Zhou; Yifan Zhang; Xueqin Wang; Gangwei Pan; Sijun Xu; Qixia Liu; Haoru Shan; Qiuxia Fu; Jianlong Ge (Chemical Engineering Journal, 2023)

General synthesis of flexible CuO nanoparticles-anchored ZrO2 nanofibrous membranes for catalytic oxidation of tetracycline - Haoru Shan; Wenqiang Wang; Zhirong Wang; Jianlong Ge; Qixia Liu; Wei Zhang; Qiuxia Fu (Chemical Engineering Journal, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

Countering beta-cypermethrin: partitioning roles of the insect gut and its bacteria - Li Bai; Xiao-Lin Cai; Man-Yu Li; Fu-Xiao Wang; Chuan-Shan Zou; Jun-Sheng Zhang; Ming-Yu Xie; Feng-Hui Qi; Tian-Zhong Jing (Journal of Pest Science, 2023)

Transcriptomics and gas chromatography-mass spectrometry metabolomics reveal the mechanism of heat shock combined with 1-methylcyclopropene to regulate the cuticle wax of jujube fruit during storage - Shuai Ge; Rongrong Wang; Lvzhu Yang; Hui Kong; Xia Chang; Xincheng Fu; Yang Shan; Shenghua Ding (Food Chemistry, 2023)

Fabrication strategies of metal–organic frameworks derivatives for catalytic aqueous pollutants elimination - Fei Wang; Ya Gao; Shan-Shan Liu; Xiao-Hong Yi; Chong-Chen Wang; Huifen Fu (Chemical Engineering Journal, 2023)

Modeling nutrient flows from land to rivers and seas – A review and synthesis - Xiaoyang Shan; Zhiqiang Zhu; Jiyong Ma; Dinghui Fu; Yanwei Song; Qipei Li; Zanhui Huang; Lixin Pei; Hongwei Zhao (Marine Environmental Research, 2023)

Regulating the reaction pathway of nZVI to improve the decontamination performance through magnetic spatial confinement effect - Hai-Yuan Chi; Xiao-Xia Zhou; Min-Rong Wu; Wan-yu Shan; Jing-fu Liu; Jin-quan Wan; Bing Yan; Rui Liu (Journal of Hazardous Materials, 2023)

Petrogenesis of the Chakabeishan pegmatites, North Qaidam Terrane: Implications for Indosinian lithium mineralization in the northern Tibetan Plateau - Jin-Heng Liu; Qiang Wang; Bing-Zhang Wang; Wu-Fu Li; Chuan-Bing Xu; Shan-Ping Li; Zi-Long Wang; Lu-Lu Hao; Tai-Zhong Song; Chun-Tao Wang; Ying Zheng; Jin-Shou Wang (Lithos, 2023)

Removal of chlorine, microparticles and water from high-viscosity liquids by a sand filter coupling hydrocyclone - Aosong Wei; Jianping Li; Minjie Shan; Wenjie Lv; Jianqi Chen; Pengbo Fu; Yanping Liu; Weichun Xu; Li Dai; Hualin Wang (Process Safety and Environmental Protection, 2023)

The ester derivatives of ferulic acid exhibit strong inhibitory effect on the growth of Alternaria alternata in vitro and in vivo - Hui Kong; Xincheng Fu; Xia Chang; Zemin Ding; Yang Yu; Haishan Xu; Rongrong Wang; Yang Shan; Shenghua Ding (Postharvest Biology and Technology, 2023)

Ultrasonication significantly enhances grafting efficiency of chitosan-ferulic acid conjugate and improves its film properties under Fenton system - Haishan Xu; Xincheng Fu; Hui Kong; Fei Chen; Xia Chang; Zemin Ding; Rongrong Wang; Yang Shan; Shenghua Ding (Food Research International, 2023)

Near-infrared I/II emission and absorption carbon dots via constructing localized excited/charge transfer state for multiphoton imaging and photothermal therapy - Wen-Bo Zhao; Dan-Dan Chen; Kai-Kai Liu; Yong Wang; Rui Zhou; Shi-Yu Song; Fu-Kui Li; Lai-Zhi Sui; Qing Lou; Lin Hou; Chong-Xin Shan (Chemical Engineering Journal, 2023)

Synthesis of amorphous Nickel-Cobalt hydroxides with high areal capacitance by one-step electrodeposition using polymeric additive - Wenxuan Hu; Huakang Fu; Lu Chen; Xing Wu; Biao Geng; Yanling Huang; Yifei Xu; Miao Du; Guorong Shan; Yihu Song; Ziliang Wu; Qiang Zheng (Chemical Engineering Journal, 2023)

The diversity and structure of diazotrophic communities in the rhizosphere of coastal saline plants is mainly affected by soil physicochemical factors but not host plant species - Yanjing Song; Lan Ma; Haiyang Zhang; Rao Fu; Xiaoyan Liang; Junlin Li; Jiajia Li; Meng Li; Yan Shan; Jieshan Cheng; Xiangyu Wang; Hongxia Zhang (Frontiers in Marine Science, 2022)
The diversity and community structure of rhizospheric microbes are largely affected by soil physicochemical properties and plant species. In this work, high throughput sequencing and quantitative real-time PCR targeting nifH gene were used to assess the abundance and diversity of diazotrophic community in the coastal saline soils of Yellow River Delta (YRD). We demonstrated that the copy number of nifH gene encoding the Fe protein subunit of the nitrogenase in the nitrogen fixation process was significantly affected by soil physiochemical factors, and the abundance of diazotrophs in the rhizospheric soil samples collected from different locations was positively related with soil physicochemical properties. Soil salinity ( P =0.003) and moisture ( P =0.003) were significantly co-varied with the OTU-based community composition of diazotrophs. Taxonomic analysis showed that most diazotrophs belonged to the Alphaproteobacteria , Gammaproteobacteria and Deltaproteobacteria . Linear discriminant analysis (LDA) effect size (LEfSe) and canonical correspondence analysis (CCA) showed that diazotrophic community structure significantly varied with soil salinity, moisture, pH and total nitrogen, carbon, sulphur and nitrite (NO 2 – N) content. Our findings provide direct evidence toward the understanding of different effects of soil physicochemical properties and host plant traits such as halophytes types, life span and cotyledon type, on the community composition of diazotrophic populations in the rhizosphere of plants grown in coastal saline soils.

Epigallocatechin-3-Gallate Pretreatment Improves Autologous Adipose-derived Stem Cells Against Rheumatoid Arthritis-induced Neuroinflammation in the Brain of Collagen-induced Rats - Ming-Shan Chen; Bruce Chi-Kang Tsai; Maria Angelina Sitorus; Chia-Hua Kuo; Wei-Wen Kuo; Tung-Sheng Chen; Chien-Yao Fu; Tsung-Jung Ho; Chih-Yang Huang; Da-Tong Ju (Neurotoxicity Research, 2022)

Exploiting the gut microbiota to predict the origins and quality traits of cultured sea cucumbers - Zelong Zhao; Jingwei Jiang; Jie Zheng; Yongjia Pan; Ying Dong; Zhong Chen; Shan Gao; Yao Xiao; Pingzhe Jiang; Xuda Wang; Gaohua Zhang; Bai Wang; et al. (Environmental Microbiology, 2022)
Summary Nowadays, the true economic and nutritional value of food is underpinned by both origin and quality traits, more often expressed as increased quality benefits derived from the origin source. Gut microbiota contribute to food metabolism and host health, therefore, it may be suitable as a qualifying indicator of origin and quality of economic species. Here, we investigated relationships between the gut microbiota of the sea cucumber ( Apostichopus japonicus ), a valuable aquaculture species in Asia, with their origins and quality metrics. Based on data from 287 intestinal samples, we generated the first biogeographical patterns for A . japonicus gut microbiota from origins across China. Importantly, A . japonicus origins were predicted using the random forest model that was constructed using 20 key gut bacterial genera, with 97.6% accuracy. Furthermore, quality traits such as saponin, fat and taurine were also successfully predicted by random forest models based on gut microbiota, with approximately 80% consistency between predicted and true values. We showed that substantial variations existed in the gut microbiota and quality variables in A . japonicus across different origins, and we also demonstrated the great potential of gut microbiota to track A . japonicus origins and predict their quality traits.

Mapping Cell Phenomics with Multiparametric Flow Cytometry Assays - Yang Liu; Haichu Zhao; Boqiang Fu; Shan Jiang; Jing Wang; Ying Wan (Phenomics, 2022)
Phenomics explores the complex interactions among genes, epigenetics, symbiotic microorganisms, diet, and environmental exposure based on the physical, chemical, and biological characteristics of individuals and groups. Increasingly efficient and comprehensive phenotyping techniques have been integrated into modern phenomics-related research. Multicolor flow cytometry technology provides more measurement parameters than conventional flow cytometry. Based on detailed descriptions of cell phenotypes, rare cell populations and cell subsets can be distinguished, new cell phenotypes can be discovered, and cell apoptosis characteristics can be detected, which will expand the potential of cell phenomics research. Based on the enhancements in multicolor flow cytometry hardware, software, reagents, and method design, the present review summarizes the recent advances and applications of multicolor flow cytometry in cell phenomics, illuminating the potential of applying phenomics in future studies.

Automatic skin lesion classification using a new densely connected convolutional network with an SF module - Pufang Shan; Chong Fu; Liming Dai; Tihui Jia; Ming Tie; Jun Liu (Medical & Biological Engineering & Computing, 2022)

The safety degree evaluation of marine biodiversity in China - Xiu-Mei Fu; Wan-Yu Wu; Fang Yang; Shan-Shan Jiang; Shi-Qi Wang; Xiao-Yan Li; Hui-Ying Tang; Ying Liu; Chang-Yun Wang (Journal of Coastal Conservation, 2022)

Lipofundin mediates major inhibition of intravenous propofol on phorbol myristate acetate and Escherichia coli-induced neutrophil extracellular traps - Ming-Shan Chen; Kung-Ssu Yang; Wen-Chun Lin; Chien-Liang Fang; Hsin-Fu Chen; Shew-Meei Sheu (Molecular Biology Reports, 2022)

A Deep Mesencephalic Nucleus Circuit Regulates Licking Behavior - Di Zheng; Jia-Yu Fu; Meng-Yu Tang; Xiao-Dan Yu; Yi Zhu; Chen-Jie Shen; Chun-Yue Li; Shi-Ze Xie; Shan Lin; Minmin Luo; Xiao-Ming Li (Neuroscience Bulletin, 2022)

Neuroprotective effect of aldose reductase knockout in a mouse model of spinal cord injury involves NF-κB pathway - Fu-xin Han; Rui Zhang; Xin-xing Yang; Shan-bo Ma; Shi-jie Hu; Bing Li (Experimental Brain Research, 2022)

Synthesis, antifungal activity and 3D-QSAR study of novel acyl thiourea compounds containing gem-dimethylcyclopropane ring - Mei Huang; Min Huang; Xiu Wang; Wen-Gui Duan; Gui-Shan Lin; Fu-Hou Lei (Molecular Diversity, 2022)

Deep Sea Water Alleviates Tau Phosphorylation and Cognitive Impairment via PI3K/Akt/GSK-3β Pathway - Shan He; Wei-Bing Peng; Xian-Jun Fu; Hong-Lei Zhou; Zhen-Guo Wang (Marine Biotechnology, 2022)

Complete genome sequencing and evolutionary analysis of hepatitis C virus subtype 6a, including strains from Guangdong Province, China - Ru Xu; Hao Wang; Jieting Huang; Min Wang; Qiao Liao; Zhengang Shan; Huishan Zhong; Xia Rong; Yongshui Fu (Archives of Virology, 2022)

A community effort to assess and improve computerized interpretation of 12-lead resting electrocardiogram - Zijian Ding; Guijin Wang; Huazhong Yang; Ping Zhang; Dapeng Fu; Zhen Yang; Xinkang Wang; Xia Wang; Zhourui Xia; Chiming Zhang; Wenjie Cai; Binhang Yuan; et al. (Medical & Biological Engineering & Computing, 2022)
Computerized interpretation of electrocardiogram plays an important role in daily cardiovascular healthcare. However, inaccurate interpretations lead to misdiagnoses and delay proper treatments. In this work, we built a high-quality Chinese 12-lead resting electrocardiogram dataset with 15,357 records, and called for a community effort to improve the performances of CIE through the China ECG AI Contest 2019. This dataset covers most types of ECG interpretations, including the normal type, 8 common abnormal types, and the other type which includes both uncommon abnormal and noise signals. Based on the Contest, we systematically assessed and analyzed a set of top-performing methods, most of which are deep neural networks, with both their commonalities and characteristics. This study establishes the benchmarks for computerized interpretation of 12-lead resting electrocardiogram and provides insights for the development of new methods.

A comparison of atmospheric geochemistry through lichens from volcanic and non-volcanic areas, north Taiwan - Le-Qi Lin; Hsueh-Yu Lu; Ju-Lien Pi; Tai-Sheng Liou; Wen-Fu Chen; Pei-Shan Hsieh (Journal of Earth System Science, 2021)

Characterization of the novel hybrid cultivar E25 of Saccharina japonica in the northern farming region of China - Li Su; Ti Feng Shan; Jing Li; Su Qin Gao; Shao Jun Pang; Xiao Fei Leng; Yan Zhang; Ming Fu Zhang; Hong Tao Gao (Journal of Applied Phycology, 2021)

Study on Tailings Covering System Constructed by Geological Polymerization of Mine Waste, Part 1: Material Characterization and Cover Construction - Yunjian Chen; Senlin Tian; Jiangli Fu; Yichao Lin; Jianhong Huang; Shan Chen; Xuewei Hu (Bulletin of Environmental Contamination and Toxicology, 2021)

Chemical constituents from the barks of Melia azedarach and their PTP1B inhibitory activity - Sheng-Nan Zhang; Lin Huang; Rui-Jing Ma; Mei-Feng Yang; Ben-Fu Wei; Hong-Zhi Song; Heng-Shan Wang; Qin-Gang Tan (Natural Product Research, 2021)

Hydrological characteristics and changes in the Nu-Salween River basin revealed with model-based reconstructed data - Fan Yang; Hui Lu; Kun Yang; Guang-wei Huang; Yi-shan Li; Wei Wang; Ping Lu; Fu-qiang Tian; Yu-gang Huang (Journal of Mountain Science, 2021)

A review of the botany, traditional uses, phytochemistry and pharmacology of Nepeta tenuifolia Briq. - Mingqiu Shan; Yulan Jiang; Yuanyuan Fu; Yongyi Zhou; Zhihui Lu; Sheng Yu; Hui Yan; Chanchan Liu; Peidong Chen; Beihua Bao; Li Zhang; Qinan Wu (Phytochemistry Reviews, 2021)

The key environmental influencing factors for the change of sediment bacterial community and antibiotics resistance genes in a long-term polluted lake, China - Lulu Zhang; Lina Shen; Zejia Ju; Yu Fu; Shan Qin; Jiansheng Cui (Ecotoxicology, 2021)

Changes of Extreme Precipitation and its Associated Mechanisms in Northwest China - Shan Lu; Zeyong Hu; Haipeng Yu; Weiwei Fan; Chunwei Fu; Di Wu (Advances in Atmospheric Sciences, 2021)

Lipidomic analyses reveal enhanced lipolysis in planthoppers feeding on resistant host plants - Xiaohong Zheng; Yeyun Xin; Yaxin Peng; Junhan Shan; Ning Zhang; Di Wu; Jianping Guo; Jin Huang; Wei Guan; Shaojie Shi; Cong Zhou; Rongzhi Chen; et al. (Science China Life Sciences, 2021)

Resource status and protection strategies of mangroves in China - Xiu-Mei Fu; Hui-Ying Tang; Yang Liu; Meng-Qi Zhang; Shan-Shan Jiang; Fang Yang; Xiao-Yan Li; Chang-Yun Wang (Journal of Coastal Conservation, 2021)
Mangrove is a typical natural landscape with great ecological, social and economic functions and values, and should be highly valued and protected. However, in the past few decades, mangrove resources have suffered serious damage, and there are also many deficiencies in mangrove protection. Chinese mangroves, as an important part of the global mangroves, are of great research value. In the present study, the status and historical dynamic process of Chinese mangrove resources were investigated and discussed to illustrate the problems of resources from three aspects, including mangrove distribution, area and plant species. Based on field research, literature research and data analysis, it was revealed that Chinese mangroves are distributed in eight provinces and regions along the southeast coast with an area of 35,749.25 hm 2 , 38 species and 40 nature reserves. The protection situation and deficiencies were analyzed from the establishment and management of nature reserves. Based on the resource status and problems, reasonable strategies were proposed to protect and manage mangroves mainly from four aspects, including publicity and education, resources restoration and protection technology, legal system establishment, and comprehensive protection and management.

Porcine circovirus type 2 (PCV2) infection in Hebei Province from 2016 to 2019: a retrospective study - Lei Han; Guang-fu Yuan; Shao-jie Chen; Fei Dai; Lin-shan Hou; Jing-hui Fan; Yu-zhu Zuo (Archives of Virology, 2021)

Tritonibacter aquimaris sp. nov. and Tritonibacter litoralis sp. nov., two novel members of the Roseobacter group isolated from coastal seawater - Na Li; Xiao-yan He; Ning-hua Liu; Tie-ji Gu; Jian Li; Yu-hui Geng; Shan Zhang; Peng Wang; Hui-hui Fu; Mei Shi; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Kelp aquaculture in China: a retrospective and future prospects - Zi‐Min Hu; Ti‐Feng Shan; Jie Zhang; Quan‐Sheng Zhang; Alan T. Critchley; Han‐Gil Choi; Norishige Yotsukura; Fu‐Li Liu; De‐Lin Duan (Reviews in Aquaculture, 2021)
Globally, China has the largest scale of kelp cultivation and production operations. However, its kelp aquaculture industry is suffering from declining germplasm diversity, degradation of agronomic traits, the presence of polluted environments, changing ocean conditions and increasing anthropological interference. This review covers two of the most commercially important kelp species in China, viz. Saccharina japonica and Undaria pinnatifida . It summarizes the history of their cultivation, production, economic and ecological benefits, their breeding programmes (e.g. inter‐ and intra‐specific hybridization and marker‐assisted selection) and efforts towards population genetic diversity and conservation. The article focuses on three significant challenges, for example genetic cross‐contamination between the wild and farmed kelp populations, ocean warming and ocean acidification. Accordingly, we outline the steps required to provide several intervention measures, for example (i) collection and preservation of wild and cultivated kelp germplasm; (ii) selection of suitable cultivation sites under changing environmental conditions; (iii) developing stress‐resistant cultivars; and finally, (iv) adoption of innovative cultivation models. The review concludes with genome‐based, designs for molecular breeding and calls for the establishment of an East Asian Kelp Consortium (EAKC). Collectively, the Chinese kelp industry could provide beneficial goods and services, for example bioenergy to fine chemicals and environmental benefits, such as carbon capture, pH amelioration and provision of habitat for many other marine species of commercial value. The strategies proposed in this article thus have the potential to not only improve but also reinvigorate the kelp industry in China and nearby Japan and Korea, in the context of both environmental health and economic benefits.

Cover Image - Zi‐Min Hu; Ti‐Feng Shan; Jie Zhang; Quan‐Sheng Zhang; Alan T. Critchley; Han‐Gil Choi; Norishige Yotsukura; Fu‐Li Liu; De‐Lin Duan (Reviews in Aquaculture, 2021)
The cover image is based on the Review Article Kelp aquaculture in China: A retrospective and future prospects by Zi‐Min Hu et al., https://doi.org/10.1111/raq.12524 . image

Spatial prediction of soil calcium carbonate content based on Bayesian maximum entropy using environmental variables - Mei Shan; Shuang Liang; Hongchen Fu; Xiaoli Li; Yu Teng; Jingwen Zhao; Yaxin Liu; Chen Cui; Li Chen; Hai Yu; Shunbang Yu; Yanling Sun; et al. (Nutrient Cycling in Agroecosystems, 2021)

Quantitative Characterization, Classification, and Influencing Factors of the Full Range of Pores in Weathering Crust Volcanic Reservoirs: Case Study in Bohai Bay Basin, China - Qingyou Yue; Xuanlong Shan; Xintao Zhang; Chunqiang Xu; Jian Yi; Mao Fu (Natural Resources Research, 2021)

Characteristics of Atmospheric Rivers over the East Asia in Middle Summers from 2001 to 2016 - Gang Fu; Shan Liu; Xiaodong Li; Pengyuan Li; Lijia Chen (Journal of Ocean University of China, 2021)

Strengthening effect of super typhoon Rammasun (2014) on upwelling and cold eddies in the South China Sea - Xue Li; Xiaolong Zhang; Dongyang Fu; Shan Liao (Journal of Oceanology and Limnology, 2021)

Effects of Cedrus atlantica extract on acute myeloid leukemia cell cycle distribution and apoptosis - Pei-Hsiu Hung; Ming-Chang Hsieh; Shan-Chih Lee; Xiao-Fan Huang; Kai-Fu Chang; Szu-Yin Chen; Ming-Shih Lee; Nu-Man Tsai (Molecular Biology Reports, 2020)

Pan-genome analysis of Paenibacillus polymyxa strains reveals the mechanism of plant growth promotion and biocontrol - Liangliang Zhou; Ting Zhang; Shan Tang; Xueqin Fu; Shuijing Yu (Antonie van Leeuwenhoek, 2020)

Analysis of the regional spectral properties in northwestern South China Sea based on an empirical orthogonal function - Dongyang Fu; Yuye Huang; Dazhao Liu; Shan Liao; Guo Yu; Xiaolong Zhang (Acta Oceanologica Sinica, 2020)

Impact of climatic factors on vegetation dynamics in the upper Yangtze River basin in China - Yu-xin Zhang; Yu-kuan Wang; Bin Fu; Amod Mani Dixit; Suresh Chaudhary; Shan Wang (Journal of Mountain Science, 2020)

Isolation, identification and character analysis of Streptococcus dysgalactiae from Megalobrama terminalis - Fei Zhao; Shan He; Ai‐ping Tan; Xue‐zhong Guo; Lan Jiang; Cui Liu‐Fu; Yu‐ting Deng; Rui‐quan Zhang (Journal of Fish Diseases, 2020)
Pure bacterial cultures were isolated from different tissues of moribund Megalobrama terminalis from a high mortality event that occurred at a farm in Foshan, China. Two isolates (F2 and F3) were identified as Streptococcus dysgalactiae subsp. dysgalactiae based on morphological and biochemical detection as well as molecular analysis. In brain heart infusion broth, the best growth conditions of isolate F3 were 35ºC, salinity 5‰ and pH 7. Furthermore, infection with isolate F3 (1.2 × 10 6 CFU/fish) led to the death of M. terminalis and zebrafish ( Danio rerio ). However, isolate F3 had no obvious pathogenicity to tilapia (GIFT, Oreochromis niloticus ). When the water temperature was 29ºC, the corresponding mortality rates for zebrafish infected by isolate F3 were higher than those at 23ºC. Culture for 24 and 72 hr with isolate F3 resulted in the same mortality rates for zebrafish. The antimicrobial susceptibility assay revealed that isolate F3 was susceptible to ampicillin, florfenicol and several other antibiotics but resistant to nalidixic acid, streptomycin, sulfamethoxazole/trimethoprim, neomycin and amikacin. To our knowledge, this is the first report that S. dysgalactiae infected the subtropical freshwater fish M. terminalis , which indicates that this bacterium is a potential threat to subtropical freshwater fish.

Adjuvant therapy with Astragalus membranaceus for post-stroke fatigue: a systematic review - Li Xu; Xiao-Yan Xu; Xue-Qin Hou; Fu-Gang Wang; Shan Gao; Han-Ting Zhang (Metabolic Brain Disease, 2020)

Changes in cultivated land patterns and driving forces in the Three Gorges Reservoir area, China, from 1992 to 2015 - Yu-xin Zhang; Yu-kuan Wang; Bin Fu; Ming Li; Ya-feng Lu; Amod Mani Dixit; Suresh Chaudhary; Shan Wang (Journal of Mountain Science, 2020)

Interferon gamma inhibits transmissible gastroenteritis virus infection mediated by an IRF1 signaling pathway - Lingling Shan; Fang Fu; Mei Xue; Xiangdong Zhu; Liang Li; Li Feng; Pinghuang Liu (Archives of Virology, 2019)

Seroprevalence of porcine bocavirus in pigs in north-central China using a recombinant-NP1-protein-based indirect ELISA - Qian-Kai Shi; Jian-Lou Zhang; Wen-Yuan Gu; Lin-Shan Hou; Guang-Fu Yuan; Shao-Jie Chen; Jing-Hui Fan; Yu-Zhu Zuo (Archives of Virology, 2019)

Hepatitis C virus 3b strains in injection drug users in Guangdong Province, China, may have originated in Yunnan Province - Min Wang; Qiao Liao; Ru Xu; Dandan Song; Jieting Huang; Qingzhu You; Zhengang Shan; Ke Huang; Xia Rong; Yongshui Fu (Archives of Virology, 2019)

Interethnic scaling of fraction unbound of a drug in plasma and volume of distribution: an analysis of extrapolation from Caucasians to Chinese - Guo Yu; Hong-Hao Zhou; Qing-Shan Zheng; Guo-Fu Li (European Journal of Clinical Pharmacology, 2019)

Identification of Gangesia oligonchis Roitman & Freze, 1964 (Cestoda: Onchoproteocephalidea) from Tachysurus fulvidraco Richardson in central China: implications for the validity of Gangesia pseudobagrae Chen, 1962 - Pei P. Fu; Wen X. Li; Hong Zou; Dong Zhang; Shan G. Wu; Ming Li; Gui T. Wang; Bing W. Xi (Systematic Parasitology, 2019)

Dynamic Responses of Bridge–Tunnel Overlapping Structure for High-Speed Railway Under Different Seismic Excitations - Guangchen Sun; Jiayou Xie; Shan He; Helin Fu; Xueliang Jiang; Liang Zheng (Geotechnical and Geological Engineering, 2019)

Overexpression of two cold-responsive ATAF-like NAC transcription factors from fine-stem stylo (Stylosanthes guianensis var. intermedia) enhances cold tolerance in tobacco plants - Peng-Lin Zhan; Shan-Wen Ke; Pan-Yu Zhang; Cong-Cong Zhou; Bei-Ling Fu; Xiang-Qian Zhang; Tian-Xiu Zhong; Shu Chen; Xin-Ming Xie (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Application of the CRISPR/Cas9 system in Dioscorea zingiberensis - Shan Feng; Wei Song; Ruirui Fu; Hong Zhang; Anran Xu; Jiaru Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Global development and trend of wind tunnel research from 1991 to 2014: a bibliometric analysis - Ziwei Mo; Hui-Zhen Fu; Yuh-Shan Ho (Environmental Science and Pollution Research, 2018)

Curcumin-loaded self-nanomicellizing solid dispersion system: part II: in vivo safety and efficacy assessment against behavior deficit in Alzheimer disease - Ankit Parikh; Krishna Kathawala; Jintao Li; Chi Chen; Zhengnan Shan; Xia Cao; Xin-Fu Zhou; Sanjay Garg (Drug Delivery and Translational Research, 2018)

Full-length and defective enterovirus G genomes with distinct torovirus protease insertions are highly prevalent on a Chinese pig farm - Yan Wang; Wen Zhang; Zhijian Liu; Xingli Fu; Jiaqi Yuan; Jieji Zhao; Yuan Lin; Quan Shen; Xiaochun Wang; Xutao Deng; Eric Delwart; Tongling Shan; et al. (Archives of Virology, 2018)

Mosaicking UAV orthoimages using bounded Voronoi diagrams and watersheds - Mengxiao Song; Zheng Ji; Shan Huang; Jing Fu (International Journal of Remote Sensing, 2018)

High-resolution melting-based TILLING of γ ray-induced mutations in rice - Shan Li; Song-mei Liu; Hao-wei Fu; Jian-zhong Huang; Qing-yao Shu (Journal of Zhejiang University-SCIENCE B, 2018)

Impacts of a Compound Amendment on Cd Immobilization, Enzyme Activities and Crop Uptake in Acidic Cd-Contaminated Paddy Soils - Shiping Shan; Zhaohui Guo; Ping Lei; Wei Cheng; Minxi Wu; Zujiao Fu; Shandong Wu; Dongxia Du; Liyang Wu (Bulletin of Environmental Contamination and Toxicology, 2018)

PGC-1α coordinates with Bcl-2 to control the cell cycle in U251 cells through reducing ROS - Kun Yao; Xu-feng Fu; Xing Du; Yan Li; Shan-shan Yang; Min Yu; Qing-hua Cui (Journal of Zhejiang University-SCIENCE B, 2018)

Highly cited articles in wind tunnel-related research: a bibliometric analysis - Ziwei Mo; Hui-Zhen Fu; Yuh-Shan Ho (Environmental Science and Pollution Research, 2018)

Revealing histological and morphological features of female reproductive system in tree shrew (Tupaia belangeri) - Shan Zhong; Shi-yao Zhang; Hui-jie Xing; Xiao-tan Zhang; Guang Wang; Yong-ping Bao; Jiang-nan Fu; Xuesong Yang (Zoomorphology, 2018)

Cropland physical disturbance intensity: plot-scale measurement and its application for soil erosion reduction in mountainous areas - Ming Li; Yu-kuan Wang; Pei Xu; Bin Fu; Cong-shan Tian; Shan Wang (Journal of Mountain Science, 2018)

Morphological and molecular divergence of Rhipicephalus turanicus tick from Albania and China - Hong-Yu Li; Shan-Shan Zhao; Sándor Hornok; Róbert Farkas; Li-Ping Guo; Chuang-Fu Chen; Ren-Fu Shao; Ji-Zhou Lv; Yuan-Zhi Wang (Experimental and Applied Acarology, 2017)

How do organ-specific metastases affect prognosis and surgical treatment for patients with metastatic upper tract urothelial carcinoma: first evidence from population based data - Fan Dong; Hangcheng Fu; Xiao Shi; Yifan Shen; Tianyuan Xu; Fengbin Gao; Xianjin Wang; Shan Zhong; Qiang Ding; Zhoujun Shen; Shanwen Chen (Clinical & Experimental Metastasis, 2017)

Characteristics and trends on global environmental monitoring research: a bibliometric analysis based on Science Citation Index Expanded - Di Zhang; Hui-Zhen Fu; Yuh-Shan Ho (Environmental Science and Pollution Research, 2017)

Development of Albumin Coupled, Cholesterol Stabilized, Lipid Nanoemulsion of Methotrexate, and TNF-α Inhibitor for Improved In Vivo Efficacy Against Rheumatoid Arthritis - Xiao-yan Li; Hui Li; Yan Zhang; Shan Gao; Chun-ping Dong; Gui-fu Wu (AAPS PharmSciTech, 2017)

Research trends and hotspots related to ammonia oxidation based on bibliometric analysis - Maosheng Zheng; Hui-Zhen Fu; Yuh-Shan Ho (Environmental Science and Pollution Research, 2017)

Associations of rs3740677 within GAB2 Gene with LOAD in Chinese Han Population - Jing-Yu Zheng; Hui-Fu Wang; Yu Wan; Meng-Shan Tan; Chen-Chen Tan; Lin Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Molecular cloning, characterization, and promoter analysis of the isochorismate synthase (AaICS1) gene from Artemisia annua - Lu-yao Wang; Ying Zhang; Xue-qing Fu; Ting-ting Zhang; Jia-wei Ma; Li-da Zhang; Hong-mei Qian; Ke-xuan Tang; Shan Li; Jing-ya Zhao (Journal of Zhejiang University-SCIENCE B, 2017)

Effects of HLA-DRB1/DQB1 Genetic Variants on Neuroimaging in Healthy, Mild Cognitive Impairment, and Alzheimer’s Disease Cohorts - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Jinyuan Liu; Yu Wan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Genetic Association of HLA Gene Variants with MRI Brain Structure in Alzheimer’s Disease - Zi-Xuan Wang; Yu Wan; Lin Tan; Jinyuan Liu; Hui-Fu Wang; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

A dramatic blood plasticity in hibernating and 14-day hindlimb unloading Daurian ground squirrels (Spermophilus dauricus) - Huan-Xin Hu; Fang-Ying Du; Wei-Wei Fu; Shan-Feng Jiang; Jin Cao; Shen-Hui Xu; Hui-Ping Wang; Hui Chang; Nandu Goswami; Yun-Fang Gao (Journal of Comparative Physiology B, 2017)

Association of DISC1 Polymorphisms with Late-Onset Alzheimer’s Disease in Northern Han Chinese - Xiao-Yan Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Ling-Li Kong; Zhan-Jie Zheng; Chen-Chen Tan; Wei Zhang; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; et al. (Molecular Neurobiology, 2017)

HLA-A2 Alleles Mediate Alzheimer’s Disease by Altering Hippocampal Volume - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Ginsenoside Rg1 promotes neural differentiation of mouse adipose-derived stem cells via the miRNA-124 signaling pathway - Juan Dong; Guo Zhu; Tian-cheng Wang; Fu-shan Shi (Journal of Zhejiang University-SCIENCE B, 2017)

SORL1 Is Associated with the Risk of Late-Onset Alzheimer’s Disease: a Replication Study and Meta-Analyses - Cheng-Cheng Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

A potential anticancer ability of 1,2-di(quinazolin-4-yl)diselane against gastric cancer cells through ROS signaling pathway - Jun Wei; Yong Yang; Zhixiang Wang; Zijian Wang; Changlai Fu; Jianqing Zhu; Jiping Shan; Yingjiu Huang; Bikui Tang; Danbin Jiang (Medicinal Chemistry Research, 2017)

Endovascular Treatment Versus Intravenous Thrombolysis for Acute Ischemic Stroke: a Quantitative Review and Meta-Analysis of 21 Randomized Trials - Chen-Chen Tan; Hui-Fu Wang; Jin-Long Ji; Meng-Shan Tan; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Impacts of CD33 Genetic Variations on the Atrophy Rates of Hippocampus and Parahippocampal Gyrus in Normal Aging and Mild Cognitive Impairment - Wen-Ying Wang; Ying Liu; Hui-Fu Wang; Lin Tan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

A Missense Variant in TREML2 Reduces Risk of Alzheimer’s Disease in a Han Chinese Population - Teng Jiang; Yu Wan; Jun-Shan Zhou; Meng-Shan Tan; Qing Huang; Xi-Chen Zhu; Huan Lu; Hui-Fu Wang; Qi Chen; Lin Tan; Ying-Dong Zhang; Lan Tan; et al. (Molecular Neurobiology, 2017)

Eliciting 10E8-like antibodies by the membrane proximal external region peptide of HIV-1 in guinea pigs - Yongjiao Yu; Lu Fu; Xin Gong; Shanshan Guan; Xiaoqiu He; He Yin; Ziyu Kuai; Wei Kong; Yuhua Shi; Yaming Shan (Biotechnology Letters, 2017)

Effect of CR1 Genetic Variants on Cerebrospinal Fluid and Neuroimaging Biomarkers in Healthy, Mild Cognitive Impairment and Alzheimer's Disease Cohorts - Xi-Chen Zhu; Hui-Fu Wang; Teng Jiang; Huan Lu; Meng-Shan Tan; Chen-Chen Tan; Lin Tan; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Association of Parkinson’s Disease GWAS-Linked Loci with Alzheimer’s Disease in Han Chinese - Xi-Chen Zhu; Lei Cao; Meng-Shan Tan; Teng Jiang; Hui-Fu Wang; Huan Lu; Chen-Chen Tan; Wei Zhang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

GWAS-Linked Loci and Neuroimaging Measures in Alzheimer’s Disease - Jie-Qiong Li; Hui-Fu Wang; Xi-Chen Zhu; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

The Impact of UNC5C Genetic Variations on Neuroimaging in Alzheimer’s Disease - Jia-Hao Sun; Hui-Fu Wang; Xi-Chen Zhu; Wan-Jiang Yu; Chen-Chen Tan; Teng Jiang; Meng-Shan Tan; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2016)

Frequency and type of inheritable mutations induced by γ rays in rice as revealed by whole genome sequencing - Shan Li; Yun-chao Zheng; Hai-rui Cui; Hao-wei Fu; Qing-yao Shu; Jian-zhong Huang (Journal of Zhejiang University-SCIENCE B, 2016)

Papaya CpERF9 acts as a transcriptional repressor of cell-wall-modifying genes CpPME1/2 and CpPG5 involved in fruit ripening - Chang-Chun Fu; Yan-Chao Han; Xiu-Ye Qi; Wei Shan; Jian-Ye Chen; Wang-Jin Lu; Jian-Fei Kuang (Plant Cell Reports, 2016)

Dietary Patterns and Risk of Dementia: a Systematic Review and Meta-Analysis of Cohort Studies - Lei Cao; Lan Tan; Hui-Fu Wang; Teng Jiang; Xi-Chen Zhu; Huan Lu; Meng-Shan Tan; Jin-Tai Yu (Molecular Neurobiology, 2016)

Impact of Common Variations in PLD3 on Neuroimaging Phenotypes in Non-demented Elders - Chong Wang; Hui-Fu Wang; Meng-Shan Tan; Ying Liu; Teng Jiang; Dao-Qiang Zhang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Education and Risk of Dementia: Dose-Response Meta-Analysis of Prospective Cohort Studies - Wei Xu; Lan Tan; Hui-Fu Wang; Meng-Shan Tan; Lin Tan; Jie-Qiong Li; Qing-Fei Zhao; Jin-Tai Yu (Molecular Neurobiology, 2016)

Genomic variability and molecular evolution of Asian isolates of sugarcane streak mosaic virus - Shan-Shan Liang; Olufemi J. Alabi; Mona B. Damaj; Wei-Lin Fu; Sheng-Ren Sun; Hua-Ying Fu; Ru-Kai Chen; T. Erik Mirkov; San-Ji Gao (Archives of Virology, 2016)

Ectomycorrhizae of Tuber huidongense and T. liyuanum with Castanea mollissima and Pinus armandii - Shan-Ping Wan; Fu-Qiang Yu; Li Tang; Ran Wang; Yun Wang; Pei-Gui Liu; Xiang-Hua Wang; Yi Zheng (Mycorrhiza, 2016)

Quantitative measurement of Parkinsonian gait from walking in monocular image sequences using a centroid tracking algorithm - Sheng-Huang Lin; Shih-Wei Chen; Yu-Chun Lo; Hsin-Yi Lai; Chich-Haung Yang; Shin-Yuan Chen; Yuan-Jen Chang; Chin-Hsing Chen; Wen-Tzeng Huang; Fu-Shan Jaw; You-Yin Chen; Siny Tsang; et al. (Medical & Biological Engineering & Computing, 2016)

MicroRNA let-7g cooperates with interferon/ribavirin to repress hepatitis C virus replication - Wen-Wen Chou; Chung-Feng Huang; Ming-Lun Yeh; Yi-Shan Tsai; Ming-Yen Hsieh; Ching-I Huang; Jee-Fu Huang; Pei-Chien Tsai; Edward Hsi; Suh-Hang Hank Juo; Wei-Lun Tsai; Wan-Long Chuang; et al. (Journal of Molecular Medicine, 2016)

Different Responses of an Invasive Clonal Plant Wedelia trilobata and its Native Congener to Gibberellin: Implications for Biological Invasion - Zhi-Cong Dai; Wei Fu; Shan-Shan Qi; De-Li Zhai; Si-Chong Chen; Ling-Yun Wan; Ping Huang; Dao-Lin Du (Journal of Chemical Ecology, 2016)

CDK6 mediates the effect of attenuation of miR-1 on provoking cardiomyocyte hypertrophy - Weiwei Yuan; Chunmei Tang; Wensi Zhu; Jiening Zhu; Qiuxiong Lin; Yongheng Fu; Chunyu Deng; Yumei Xue; Min Yang; Shulin Wu; Zhixin Shan (Molecular and Cellular Biochemistry, 2016)

Chronic Metformin Preconditioning Provides Neuroprotection via Suppression of NF-κB-Mediated Inflammatory Pathway in Rats with Permanent Cerebral Ischemia - Xi-Chen Zhu; Teng Jiang; Qiao-Quan Zhang; Lei Cao; Meng-Shan Tan; Hui-Fu Wang; Zheng-Zheng Ding; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2015)

Polymorphic microsatellite loci in the Chinese skink, Plestiodon chinensis (squamata: scincidae) - Tian-qi Fan; Tian-long Fu; Yan-xia Zhang; Hong-liang Lu; Chao-nan Zhu; Shan Sun; Hong Li (Conservation Genetics Resources, 2015)

The potential mechanism of bursal-derived BP8 on B cell developments - Xiao-Dong Liu; Fu-Bo Zhang; Hu Shan; Pu-Yan Chen (Biotechnology Letters, 2015)

Isolation and characterization of microsatellite markers in the Asiatic water snake (Xenochrophis piscator) - Zong-Shi Zhou; Tian-Long Fu; Chao-Nan Zhu; Shan Sun; Yan-Fu Qu (Conservation Genetics Resources, 2015)

Ischemic Preconditioning Provides Neuroprotection by Induction of AMP-Activated Protein Kinase-Dependent Autophagy in a Rat Model of Ischemic Stroke - Teng Jiang; Jin-Tai Yu; Xi-Chen Zhu; Qiao-Quan Zhang; Meng-Shan Tan; Lei Cao; Hui-Fu Wang; Jian-Quan Shi; Li Gao; Hao Qin; Ying-Dong Zhang; Lan Tan (Molecular Neurobiology, 2015)

Experimental Study of the Effect on Bone Metabolism and Bone Histomorphometry of Osteoporosis Rats with Birdpecking and Revolving Moxibustion on Twelve Back-Shu Points - Hong-Shi Zhang; Tie Li; Xing-Shan Liu; Fu-Chun Wang; Xin Yao; Li Yan; Wu-Jin Liang (Cell Biochemistry and Biophysics, 2015)

mTOR ATP-competitive inhibitor INK128 inhibits neuroblastoma growth via blocking mTORC signaling - Huiyuan Zhang; Jun Dou; Yang Yu; Yanling Zhao; Yihui Fan; Jin Cheng; Xin Xu; Wei Liu; Shan Guan; Zhenghu Chen; Yan shi; Roma Patel; et al. (Apoptosis, 2015)

The caspase-8 shRNA-modified mesenchymal stem cells improve the function of infarcted heart - Yeyou Liang; Qiuxiong Lin; Jiening Zhu; Xiaohong Li; Yongheng Fu; Xiao Zou; Xiaoying Liu; Honghong Tan; Chunyu Deng; Xiyong Yu; Zhixin Shan; Weiwei Yuan (Molecular and Cellular Biochemistry, 2014)

Optimal intervention time of vagal stimulation attenuating myocardial ischemia/reperfusion injury in rats - Qiang Wang; Rui-Ping Li; Fu-Shan Xue; Shi-Yu Wang; Xin-Long Cui; Yi Cheng; Gao-Pu Liu; Xu Liao (Inflammation Research, 2014)

Similarities and Differences in Gastrointestinal Physiology Between Neonates and Adults: a Physiologically Based Pharmacokinetic Modeling Perspective - Guo Yu; Qing-Shan Zheng; Guo-Fu Li (The AAPS Journal, 2014)

Characteristics of Rocky Basin Structure of Yongshu Reef in the Southern South China Sea - Qing-Shan Meng; Ke-Fu Yu; Ren Wang; Yue Qin; Hou-Zhen Wei; Xin-Zhi Wang (Marine Georesources & Geotechnology, 2014)

Accumulation of FLT3+ CD11c+ dendritic cells in psoriatic lesions and the anti-psoriatic effect of a selective FLT3 inhibitor - Heng-Xiu Yan; Wei-Wei Li; Yan Zhang; Xia-Wei Wei; Li-Xin Fu; Guo-Bo Shen; Tao Yin; Xiu-Ying Li; Hua-Shan Shi; Yang Wan; Qing-Yin Zhang; Jiong Li; et al. (Immunologic Research, 2014)

Isolation and characterization of microsatellite loci in the endangered Amur ratsnake Elaphe schrenckii (Reptilia; Squamata; Colubridae) from China - Xue-yang Xu; Tian-long Fu; Yan-Fu Qu; Xiao-xiao Zheng; Chao-nan Zhu; Shan Sun; Hong Li (Conservation Genetics Resources, 2014)

Co-delivery of Dexamethasone and Green Tea Polyphenols Using Electrospun Ultrafine Fibers for Effective Treatment of Keloid - Jinrong Li; Rong Fu; Long Li; Guang Yang; Shan Ding; Zhendong Zhong; Shaobing Zhou (Pharmaceutical Research, 2014)

MicroRNA-30c serves as an independent biochemical recurrence predictor and potential tumor suppressor for prostate cancer - Xiao-hui Ling; Zhao-dong Han; Dan Xia; Hui-chan He; Fu-neng Jiang; Zhuo-yuan Lin; Xin Fu; Ye-han Deng; Qi-shan Dai; Chao Cai; Jia-hong Chen; Yu-xiang Liang; et al. (Molecular Biology Reports, 2014)

Distribution of Polychlorinated Biphenyls in Soil Around Three Typical Industrial Sites in Beijing, China - Yong-Fei Zhang; Shan Fu; Yuan Dong; Hai-Feng Nie; Zheng Li; Xin-Chun Liu (Bulletin of Environmental Contamination and Toxicology, 2014)

Model-based optimisation of nitrogen and water management for wheat–maize systems in the North China Plain - Anna Michalczyk; Kurt Christian Kersebaum; Marco Roelcke; Tobias Hartmann; Shan-Chao Yue; Xin-Ping Chen; Fu-Suo Zhang (Nutrient Cycling in Agroecosystems, 2014)

Altered miRNA Expression is Associated with Differentiation, Invasion, and Metastasis of Esophageal Squamous Cell Carcinoma (ESCC) in Patients from Huaian, China - Hai Long Fu; De Ping Wu; Xiu Fang Wang; Jian Guo Wang; Feng Jiao; Lei Lei Song; Hui Xie; Xu Yang Wen; Hu Sheng Shan; Yun Xiang Du; Ya Ping Zhao (Cell Biochemistry and Biophysics, 2013)

The short chain cell-permeable ceramide (C6) restores cell apoptosis and perifosine sensitivity in cultured glioblastoma cells - Li-sen Qin; Zheng-quan Yu; Shi-ming Zhang; Guan Sun; Jian Zhu; Jin Xu; Jun Guo; Lin-shan Fu (Molecular Biology Reports, 2013)

miR-155 inhibits oxidized low-density lipoprotein-induced apoptosis of RAW264.7 cells - Guo-fu Zhu; Li-xia Yang; Rui-wei Guo; Hong Liu; Yan-kun Shi; Hong Wang; Jin-shan Ye; Zhi-hua Yang; Xing Liang (Molecular and Cellular Biochemistry, 2013)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

A two-tube multiplex real-time RT-PCR assay for the detection of four hemorrhagic fever viruses: severe fever with thrombocytopenia syndrome virus, Hantaan virus, Seoul virus, and dengue virus - Zhifeng Li; Xian Qi; Minghao Zhou; Changjun Bao; Jianli Hu; Bin Wu; Shenjiao Wang; Zhongmin Tan; Jianguang Fu; Jun Shan; Yefei Zhu; Fenyang Tang (Archives of Virology, 2013)

RP105 involved in activation of mouse macrophages via TLR2 and TLR4 signaling - Bo Liu; Naisheng Zhang; Zhicheng Liu; Yunhe Fu; Shuang Feng; Shan Wang; Yongguo Cao; Depeng Li; Dejie Liang; Fengyang Li; Xiaojing Song; Zhengtao Yang (Molecular and Cellular Biochemistry, 2013)

Screening Chinese soybean genotypes for Agrobacterium-mediated genetic transformation suitability - Zhang-yue Song; Jing-luan Tian; Wei-zhe Fu; Lin Li; Ling-hong Lu; Lian Zhou; Zhi-hui Shan; Gui-xiang Tang; Hui-xia Shou (Journal of Zhejiang University-SCIENCE B, 2013)

Molecular Cloning and Polymorphism of the Major Histocompatibility Complex (MHC) Class IIB Gene of Grass Carp (Ctenopharyngodon idella) - Zhong-Dian Dong; Yan Zhao; Qi Fan Zeng; Yong Fu; Fen Na Zhou; Xiang Shan Ji; Hui Wang (Biochemical Genetics, 2013)

Grain and shoot zinc accumulation in winter wheat affected by nitrogen management - Yan-Fang Xue; Shan-Chao Yue; Yue-Qiang Zhang; Zhen-Ling Cui; Xin-Ping Chen; Fu-Chun Yang; Ismail Cakmak; Steve P. McGrath; Fu-Suo Zhang; Chun-Qin Zou (Plant and Soil, 2012)

A comparison of the ultrastructure and composition of fruits’ cuticular wax from the wild-type ‘Newhall’ navel orange (Citrus sinensis [L.] Osbeck cv. Newhall) and its glossy mutant - De-Chun Liu; Qiong Zeng; Qing-Xun Ji; Chuan-Fu Liu; Shan-Bei Liu; Yong Liu (Plant Cell Reports, 2012)

Contribution of SATB2 to the stronger osteogenic potential of bone marrow stromal cells from craniofacial bones - Ping Zhang; Jie Men; Yu Fu; Tengfei Shan; Jinhai Ye; Yunong Wu; Zhenjiang Tao; Laikui Liu; Hongbing Jiang (Cell and Tissue Research, 2012)

Postconditioning with vagal stimulation attenuates local and systemic inflammatory responses to myocardial ischemia reperfusion injury in rats - Qiang Wang; Yi Cheng; Fu-Shan Xue; Yu-Jing Yuan; Jun Xiong; Rui-Ping Li; Xu Liao; Jian-Hua Liu (Inflammation Research, 2012)

Anomalous temperature–growth response of Abies faxoniana to sustained freezing stress along elevational gradients in China’s Western Sichuan Province - Zong Shan Li; Guo Hua Liu; Bo Jie Fu; Chan Juan Hu; Shu Zheng Luo; Xing Liang Liu; Fei He (Trees, 2012)

Five novel species of the anamorphic genus Candida in the Cyberlindnera clade isolated from natural substrates in Taiwan - Chin-Feng Chang; Yi-Ru Liu; Shan-Fu Chen; Gennadi I. Naumov; Elena S. Naumova; Ching-Fu Lee (Antonie van Leeuwenhoek, 2012)

Induced bone marrow mesenchymal stem cells improve cardiac performance of infarcted rat hearts - Xiao-Hong Li; Yong-Heng Fu; Qiu-Xiong Lin; Zai-Yi Liu; Zhi-Xin Shan; Chun-Yu Deng; Jie-Ning Zhu; Min Yang; Shu-Guang Lin; Yangxin Li; Xi-Yong Yu (Molecular Biology Reports, 2012)

Clinical Study of Autologous Cytokine-Induced Killer Cells for the Treatment of Elderly Patients with Diffuse Large B-Cell Lymphoma - Xue-chun Lu; Bo Yang; Rui-li Yu; Xiao-hua Chi; Shuai Tuo; Chao-wei Tuo; Hong-li Zhu; Yao Wang; Chao-guang Jiang; Xiao-bing Fu; Yang Yang; Yang Liu; et al. (Cell Biochemistry and Biophysics, 2012)

Laser-induced withdrawal test for electrophysiological recordings of nociception - Yu-Chieh Kao; Fu-Shan Jaw (Journal of Comparative Physiology A, 2012)

The Potential Influence of Seasonal Climate Variables on the Net Primary Production of Forests in Eastern China - Zong Shan Li; Guo Hua Liu; Bo Jie Fu; Jin Long Zhang (Environmental Management, 2011)

Polycyclic aromatic hydrocarbons in surface sediments of the Jialu River - Jie Fu; Sheng Sheng; Teng Wen; Zhi-Ming Zhang; Qing Wang; Qiu-Xiang Hu; Qing-Shan Li; Shu-Qing An; Hai-Liang Zhu (Ecotoxicology, 2011)

Comparison of cardioprotective and anti-inflammatory effects of ischemia pre- and postconditioning in rats with myocardial ischemia–reperfusion injury - Jun Xiong; Qiang Wang; Fu-Shan Xue; Yuan-Jing Yuan; Shan Li; Jian-Hua Liu; Xu Liao; Yan-Ming Zhang (Inflammation Research, 2011)

Characterization of Exserohilum rostratum, a new causal agent of banana leaf spot disease in China - Shan-Hai Lin; Si-Liang Huang; Qi-Qin Li; Chun-Jin Hu; Gang Fu; Li-Ping Qin; Yue-Feng Ma; Ling Xie; Zhen-Lu Cen; Wei-Hong Yan (Australasian Plant Pathology, 2011)

Special Distribution of Polybrominated Diphenyl Ethers in Brain Tissues of Free-range Domestic Hens and Ducks from a Village near an Electronic Waste Recycling Site in South China - Zhong-Zhi Yang; Yong-Fang Li; Shan Fu; Xing-Ru Zhao (Bulletin of Environmental Contamination and Toxicology, 2011)

The impact of naturalized legumes on plant communities in Northern Taiwan: are we worrying too much? - Jenn-Kuo Tsai; Hao-Ting Sun; Chiao-Fen Chen; Chang-Fu Hsieh; Shan-Huah Wu (Plant Ecology, 2010)

Preliminary study on the freeze-drying of human bone marrow-derived mesenchymal stem cells - Shao-zhi Zhang; Huan Qian; Zhen Wang; Ju-li Fan; Qian Zhou; Guang-ming Chen; Rui Li; Shan Fu; Jie Sun (Journal of Zhejiang University-SCIENCE B, 2010)

Lowland rainforests in southern Taiwan and Lanyu, at the northern border of Paleotropics and under the influence of monsoon wind - Wei-Chun Chao; Guo-Zhang M. Song; Kuo-Jung Chao; Chi-Cheng Liao; Su-Wei Fan; Shan-Huah Wu; Tsung-Hsin Hsieh; I-Fang Sun; Yau-Lun Kuo; Chang-Fu Hsieh (Plant Ecology, 2010)

Erratum to: Early administration of propofol protects against endotoxin-induced acute lung injury in rats by inhibiting the TGF-β1-Smad2 dependent pathway - Ju Gao; Wei-Xian Zhao; Fu-Shan Xue; Luo-Jing Zhou; Shao-qun Xu; Ning Ding (Inflammation Research, 2010)

Early administration of propofol protects against endotoxin-induced acute lung injury in rats by inhibiting the TGF-β1-Smad2 dependent pathway - Ju Gao; Wei-Xian Zhao; Fu-Shan Xue; Luo-Jing Zhou; Shao-qun Xu; Ning Ding (Inflammation Research, 2010)

Spatial Characteristics and Major Sources of Polycyclic Aromatic Hydrocarbons from Soil and Respirable Particulate Matter in a Mega-City, China - Shan Fu; Zhong-Zhi Yang; Ke Li; Xiao-Bai Xu (Bulletin of Environmental Contamination and Toxicology, 2010)

Patterns of plant invasions in China: Taxonomic, biogeographic, climatic approaches and anthropogenic effects - Shan-Huah Wu; Hao-Ting Sun; Yung-Ching Teng; Marcel Rejmánek; Shu-Miaw Chaw; T.-Y. Aleck Yang; Chang-Fu Hsieh (Biological Invasions, 2010)

Analysis of Brassica rapa ESTs: gene discovery and expression patterns of AP2/ERF family genes - Jing Zhuang; Ai-Sheng Xiong; Ri-He Peng; Feng Gao; Bo Zhu; Jian Zhang; Xiao-Yan Fu; Xiao-Feng Jin; Jian-Min Chen; Zhen Zhang; Yu-Shan Qiao; Quan-Hong Yao (Molecular Biology Reports, 2010)

Twelve novel polymorphic microsatellite loci developed from the Asiatic black bear (Ursus thibetanus) - Hua Wu; Shan-Ning Zhang; Fu-Wen Wei (Conservation Genetics, 2010)

Fluorescent Property of the Gd3+-Doped Terbium Complexes and Crystal Structure of [Tb(TPTZ)(H2O)6]Cl3·3H2O - Yan-Fang Zhao; Yong-Liang Zhao; Feng Bai; Xiao-yan Wei; Yong-sheng Zhou; Mei-na Shan; Huan-huan Li; Rui-jun Ma; Xiao-tao Fu; Yan Du (Journal of Fluorescence, 2010)

Comparison of approaches for efficient gene silencing induced by microRNA-based short hairpin RNA and indicator gene expression - Z. X. Shan; Q. X. Lin; C. Y. Deng; Z. L. Zhou; H. H. Tan; Y. H. Fu; X. H. Li; J. N. Zhu; L. P. Mai; S. J. Kuang; S. G. Lin; X. Y. Yu (Molecular Biology Reports, 2010)

Protective effect of selaginellin on glutamate-induced cytotoxicity and apoptosis in differentiated PC12 cells - Chen-Jing Wang; Chang-Ping Hu; Kang-Ping Xu; Qiong Yuan; Fu-Shuang Li; Hui Zou; Gui-Shan Tan; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Undisturbed Strata Succession Sampling Technology and the Engineering Geological Characteristics of an Atoll in the Southern South China Sea - Qing-Shan Meng; Ren Wang; Ke-Fu Yu; Ming-Jian Hu; Xin-Zhi Wang; Chao Yang (Marine Georesources & Geotechnology, 2009)

An efficient method to enhance gene silencing by using precursor microRNA designed small hairpin RNAs - Zhixin Shan; Qiuxiong Lin; Chunyu Deng; Xiaohong Li; Wei Huang; Honghong Tan; Yongheng Fu; Min Yang; Xi-Yong Yu (Molecular Biology Reports, 2009)

Phenotypic diversity of the big seed type subcollection of wild soybean (Glycine soja Sieb. et Zucc.) in China - Ke-Jing Wang; Xiang-Hua Li; Fu-Shan Li (Genetic Resources and Crop Evolution, 2008)

Adrenal myelolipoma within myxoid cortical adenoma associated with Conn’s syndrome - Lu Hong-sheng; Gan Mei-fu; Chen Han-song; Huang Shan-qiang (Journal of Zhejiang University-SCIENCE B, 2008)

Selection of DNA aptamers against DC-SIGN protein - Yan Hui; Li Shan; Zhou Lin-fu; Zhu Jian-hua (Molecular and Cellular Biochemistry, 2007)

Analysis of wheat-Thinopyrum intermedium derivatives with BYDV-resistance - Zhi-Shan Lin; Zhi-Fu Cui; Xiang-Yan Zeng; You-Zhi Ma; Zeng-Yan Zhang; Toshiki Nakamura; Goro Ishikawa; Kazuhiro Nakamura; Hisashi Yoshida; Zhi-Yong Xin (Euphytica, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Two new flavanes and bioactive compounds from Daphne tangutica Maxim - W. Zhang; Y. H. Shen; Z. Y. Lou; R. H. Liu; C. Zhang; P. Fu; L. Shan; W. D. Zhang (Natural Product Research, 2007)

Incidental discovery of high systemic lupus erythematosus disease activity associated with cytomegalovirus viral activity - Ben Yu-Jih Su; Cheng-Yu Su; Shan-Fu Yu; Chung-Jen Chen (Medical Microbiology and Immunology, 2007)

Measurement of soluble solids content in watermelon by Vis/NIR diffuse transmittance technique - Hai-qing Tian; Yi-bin Ying; Hui-shan Lu; Xia-ping Fu; Hai-yan Yu (Journal of Zhejiang University-SCIENCE B, 2007)

Two new chemical constituents from Daphne odora Thunb. var. marginata - W. Zhang; W. D. Zhang; R. H. Liu; Y. H. Shen; C. Zhang; H. S. Cheng; P. Fu; L. Shan (Natural Product Research, 2006)

Application Fourier transform near infrared spectrometer in rapid estimation of soluble solids content of intact citrus fruits - Hui-shan Lu; Hui-rong Xu; Yi-bin Ying; Xia-ping Fu; Hai-yan Yu; Hai-qing Tian (Journal of Zhejiang University-SCIENCE B, 2006)

Soil microbial biomass as affected by non-flooded plastic mulching cultivation in rice - Yong-Shan Li; Liang-Huan Wu; Xing-Hua Lu; Li-Mei Zhao; Qiao-Lan Fan; Fu-Suo Zhang (Biology and Fertility of Soils, 2006)

Distribution of HCHs and DDTs in Soils from Beijing City, China - Xinghong Li; Youfeng Zhu; Xiufen Liu; Shan Fu; Xiaobai Xu; Hangxin Cheng (Archives of Environmental Contamination and Toxicology, 2006)

Absence of CYP2B6 promoter −82T>C mutation in Chinese as an additional factor for slow metabolism of drugs commonly used in infections - Ming-liang He; CK Lin; Kenneth Tong; Bingying Xu; Joseph JY Sung; Hsiang-fu Kung; Shui-shan Lee (European Journal of Clinical Pharmacology, 2006)

Salicylic Acid Enhances Jaceosidin and Syringin Production in Cell Cultures of Saussurea medusa - Zhen-Zhen Yu; Chun-Xiang Fu; Ying-Shan Han; Yong-Xing Li; De-Xiu Zhao (Biotechnology Letters, 2006)

Development of SCAR and CAPS Markers for a Partially Dominant Yellow Seed Coat Gene in Brassica Napus L - Zhiwen Liu; Tingdong Fu; Ying Wang; Jinxing Tu; Baoyuan Chen; Yongming Zhou; Chaozhi Ma; Lianmin Shan (Euphytica, 2006)

A comparison between hairy root cultures and wild plants of Saussurea involucrata in phenylpropanoids production - Chun-Xiang Fu; Yan-jun Xu; De-Xiu Zhao; Feng Shan Ma (Plant Cell Reports, 2006)

Detecting Epstein-Barr virus DNA from peripheral blood mononuclear cells in adult patients with systemic lupus erythematosus in Taiwan - Shan-Fu Yu; Huei-Chuin Wu; Wen-Chan Tsai; Jeng-Hsien Yen; Wen Chiang; Chung-Yee Yuo; Sheng-Nan Lu; Lien-Chai Chiang; Chung-Jen Chen (Medical Microbiology and Immunology, 2005)

Cellular aggregate size as the critical factor for flavonoid production by suspension cultures of Saussurea medusa - Chun-xiang Fu; De-xiu Zhao; Yan Huang; Feng-shan Ma (Biotechnology Letters, 2005)

Study on the framework system of digital agriculture - Yong Liang; Xiu-shan Lu; De-gui Zhang; Fu Liang; Zhi-bo Ren (Chinese Geographical Science, 2003)

Effect of apple production base on regional water cycle in Weibei upland of the Loess Plateau - Huang Ming-bin; He Fu-hong; Yang Xin-min; Li Yu-shan (Journal of Geographical Sciences, 2001)

Synthesis, structure and anti-acetylcholinesterase activity of 4β-methoxymethyl-4β-demethyl territrem B - Fu-Chuo Peng; Jur-Shan Cheng (Mycopathologia, 1997)